Crosslinked resin particles and method for producing the same
Biodegradable crosslinked resin particles are produced by crosslinking polyhydroxyalkanoate resin in an aqueous dispersion with peroxides, addressing the lack of such particles in existing technologies and offering enhanced mechanical properties and environmental sustainability.
Patent Information
- Application Number
- JP2023172671
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-04
- Publication Date
- 2025-04-16
AI Technical Summary
There is no known method for producing biodegradable crosslinked resin particles.
The production of crosslinked resin particles is achieved by using polyhydroxyalkanoate resin with a crosslinked structure, a gel fraction of 50% or more, and a protein content of 200 to 20,000 ppm, which are then crosslinked using peroxides in an aqueous dispersion.
This method provides biodegradable crosslinked resin particles with improved mechanical properties, such as tensile impact strength, and reduced environmental impact, contributing to sustainable development goals.
Smart Images

Figure 2025063458000001 
Figure 2025063458000002 
Figure 2025063458000003
Abstract
Description
[Technical field]
[0001] The present invention relates to crosslinked resin particles and a method for producing the same. [Background technology]
[0002] 2. Description of the Related Art Conventionally, techniques for adding various modifiers (for example, crosslinked particles) to thermoplastic resins in order to improve the mechanical strength, such as the impact strength, of thermoplastic resins have been known.
[0003] Known examples of crosslinked resin particles include crosslinked resin particles made of resins such as acrylic resins, acrylic silicone resins, and polystyrene (see, for example, Patent Documents 1 and 2).
[0004] Meanwhile, in recent years, from the viewpoint of consideration for the environment during and after the disposal of resin products, there has been active development of biodegradable resins (hereinafter, sometimes referred to as "biodegradable resins"). For example, Patent Document 3 describes crosslinking of poly(3-hydroxyalkanoate), a type of biodegradable resin, by melt-kneading the resin in the presence of an organic peroxide. However, it describes that the crosslinked resin produced by such melt-kneading is used to constitute a film and / or sheet, and there is no description at all about producing crosslinked resin particles. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2009-56770 A [Patent Document 2] JP 2003-82191 A [Patent Document 3] International Publication No. 2019 / 022008 Summary of the Invention [Problem to be solved by the invention]
[0006] So far, no biodegradable crosslinked resin particles have been known.
[0007] An embodiment of the present invention has been made in consideration of the above-mentioned current situation, and an object of the invention is to provide novel crosslinked resin particles having biodegradability. [Means for solving the problem]
[0008] In order to solve the above problems, one embodiment of the present invention includes the following configuration. [1] Crosslinked resin particles containing a polyhydroxyalkanoate resin having a crosslinked structure, the crosslinked resin particles having a gel fraction of 50% or more and a protein content of 200 to 20,000 ppm. [2] The crosslinked resin particles according to [1], having a volume average particle size of 0.1 μm to 10 μm. [3] The crosslinked resin particles according to [1] or [2], wherein the polyhydroxyalkanoate resin is a poly(3-hydroxyalkanoate) resin. [4] The crosslinked resin particles according to any one of [1] to [3], wherein the proportion of the polyhydroxyalkanoate resin in the crosslinked resin particles is 80% by weight or more. [5] The crosslinked resin particles according to any one of [1] to [4], wherein the gel fraction is 70 to 100%. [6] The crosslinked resin particles according to any one of [1] to [5], wherein the crosslinked resin particles are crosslinked using a peroxide. [7] The crosslinked resin particles according to [6], wherein the crosslinked resin particles are crosslinked in the presence of the peroxide and a polyfunctional compound. [8] The crosslinked resin particles according to any one of [1] to [7], wherein the crosslinked resin particles are not foamed. [9] A method for producing crosslinked resin particles which contains a polyhydroxyalkanoate resin having a crosslinked structure and has a gel fraction of 50% or more, the method comprising the steps of: preparing an aqueous dispersion containing polyhydroxyalkanoate resin particles having a protein content of 200 to 20,000 ppm; an impregnation step of adding a peroxide to the aqueous dispersion of PHA particles to impregnate the polyhydroxyalkanoate resin particles with the peroxide; and a crosslinking step of heating the aqueous dispersion of resin particles impregnated with the peroxide to a heating temperature to crosslink molecular chains of the polyhydroxyalkanoate resin in the polyhydroxyalkanoate resin particles.
[10] A thermoplastic resin composition comprising a thermoplastic resin and the crosslinked resin particles according to any one of [1] to [8].
[11] The thermoplastic resin composition according to
[10] , further comprising a crystal nucleating agent and / or a lubricant.
[12] A molded article obtained by molding the thermoplastic resin composition according to
[11] or
[12] .
[13] A method for producing a thermoplastic resin composition, comprising a mixing step of mixing a thermoplastic resin and the crosslinked resin particles according to any one of [1] to [8].
[14] The method for producing a thermoplastic resin composition according to
[13] , wherein a crystal nucleating agent and / or a lubricant is further mixed in the mixing step. Effect of the Invention
[0009] According to one embodiment of the present invention, it is possible to provide a novel crosslinked resin particle having biodegradability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] An embodiment of the present invention will be described below, but the present invention is not limited thereto. The present invention is not limited to each configuration described below, and various modifications are possible within the scope of the claims. In addition, embodiments or examples obtained by combining the technical means disclosed in different embodiments or examples are also included in the technical scope of the present invention. Furthermore, new technical features can be formed by combining the technical means disclosed in each embodiment. All academic documents and patent documents described in this specification are incorporated herein by reference. In addition, unless otherwise specified in this specification, "A to B" representing a numerical range means "A or more (including A and greater than A) and B or less (including B and smaller than B)".
[0011] [1. Crosslinked resin particles] The crosslinked resin particles according to one embodiment of the present invention are crosslinked resin particles containing a polyhydroxyalkanoate resin, and have a gel fraction of 50% or more and a protein content of 200 to 20,000 ppm.
[0012] In this specification, "polyhydroxyalkanoate resin" may be referred to as "PHA," "polyhydroxyalkanoate resin particles" may be referred to as "PHA particles," and "crosslinked resin particles according to one embodiment of the present invention" may be referred to as "the present crosslinked resin particles."
[0013] In the course of intensive research to provide crosslinked resin particles of PHA, the present inventors have found that, when crosslinking PHA particles, the protein content of the PHA particles is controlled within a specific range, thereby making it possible to crosslink PHA while ensuring aggregation stability. In addition, the present inventors have found that the crosslinked resin particles obtained by this method, the protein content of which is controlled within the above-mentioned specific range, can be added to a thermoplastic resin to provide a thermoplastic resin composition capable of providing a molded product with improved tensile impact strength, color tone, etc., and have thus completed the present invention.
[0014] The crosslinked resin particles of the present invention are biodegradable because they contain polyhydroxyalkanoate resin, which is a biodegradable plastic. Therefore, they are expected to be useful as crosslinked resin particles that are friendly to the global environment and can address the problem of plastic waste. For example, by using the crosslinked resin particles obtained by the present production method for the application of a resin composition or a molded article, a resin composition or molded article having biodegradability can be provided, and as a result, soil pollution and / or marine pollution when these are discarded can be suppressed. That is, one embodiment of the present invention is expected to contribute to the achievement of the Sustainable Development Goals (SDGs), such as Goal 12 "Ensure sustainable consumption and production patterns" and / or Goal 14 "Conserve and sustainably use the oceans and marine resources for sustainable development".
[0015] In a preferred embodiment of the present invention, a molded article obtained by molding a resin composition containing crosslinked resin particles obtained by the present production method and a thermoplastic resin also has an advantage of being excellent in tensile impact strength.
[0016] In this specification, the term "crosslinked resin particles" refers to resin particles having a crosslinked structure in which molecular chains of the resin (PHA in the present crosslinked resin particles) constituting the resin particles are bonded to each other. In other words, the present crosslinked resin particles have a crosslinked structure in which molecular chains of PHA are bonded to each other.
[0017] Each component that the present crosslinked resin particles may contain will be described in detail below.
[0018] (Polyhydroxyalkanoate resin) The crosslinked resin particles of the present invention contain a polyhydroxyalkanoate resin (PHA) having a crosslinked structure. In this specification, the term "PHA having a crosslinked structure" refers to a PHA having a structure in which the molecular chains of two or more PHA molecules are bonded to each other.
[0019] "PHA" is a general term for polymers containing hydroxyalkanoic acid as a monomer unit (monomer repeating unit), and is generally biodegradable. PHA is an aliphatic polyester, preferably a polyester not containing an aromatic ring. In this specification, "PHA" refers to a polymer containing hydroxyalkanoic acid repeating units in an amount of 50 mol% or more of all monomer repeating units (100 mol%). PHA preferably contains hydroxyalkanoic acid repeating units in an amount of 60 mol% or more, more preferably 70 mol% or more, of all monomer repeating units (100 mol%).
[0020] There is no particular limitation on the PHA. Examples of PHA include polyglycolic acid, poly(3-hydroxyalkanoate)-based resin (hereinafter sometimes referred to as "P3HA"), poly(4-hydroxyalkanoate)-based resin, etc. PHA may be used alone or in combination of two or more types. The present crosslinked resin particles preferably contain a poly(3-hydroxyalkanoate)-based resin as a PHA component, and more preferably the PHA component contained in the present crosslinked resin particles is a poly(3-hydroxyalkanoate)-based resin (in other words, the PHA component contained in the present crosslinked resin particles contains only a poly(3-hydroxyalkanoate)-based resin).
[0021] The polyglycolic acid may be a homopolymer of glycolic acid, or a copolymer of glycolic acid and a monomer other than glycolic acid (for example, a copolymer of glycolic acid and lactic acid, a copolymer of glycolic acid and caprolactone, etc.).
[0022] Polyglycolic acid can be obtained by known methods such as condensation polymerization of glycolic acid and ring-opening polymerization of glycolide.
[0023] The P3HA has the formula: [-CHR-CH 2 -CO-O-] (wherein R is C n H 2n+1where n is an integer of 1 to 15.) is a polyhydroxyalkanoate containing as an essential repeating unit. In this specification, "P3HA" refers to a resin containing 50 mol % or more of the 3-hydroxyalkanoic acid repeating units out of all monomer repeating units (100 mol %). Since it has excellent biodegradability and can be produced using renewable biomass resources as raw materials, it is effective in reducing the environmental load, and therefore it is preferable that the present crosslinked resin particles contain P3HA as a PHA component.
[0024] The P3HA preferably contains 60 mol % or more, and more preferably 70 mol % or more, of the 3-hydroxyalkanoic acid repeating units out of all monomer repeating units (100 mol %).
[0025] P3HA is not particularly limited, and may be a homopolymer containing the repeating unit described above, or a copolymer containing the repeating unit described above. Examples of the copolymer include copolymers of 3-hydroxybutanoic acid (hereinafter sometimes referred to as "3HB") and one or more monomers selected from the group consisting of 3-hydroxypropionic acid, 3-hydroxypentanoic acid, 3-hydroxyhexanoic acid, 3-hydroxyheptanoic acid, 3-hydroxyoctanoic acid, 3-hydroxynonanoic acid, 3-hydroxydecanoic acid, 3-hydroxyundecanoic acid, 3-hydroxydodecanoic acid, 3-hydroxytridecanoic acid, 3-hydroxytetradecanoic acid, 3-hydroxyhexadecanoic acid, and 3-hydroxyoctadecanoic acid. Alternatively, another example of the copolymer may be, for example, a copolymer of 3HB and one or more monomers selected from the group consisting of 4-hydroxybutanoic acid, 4-hydroxypentanoic acid, 4-hydroxyhexanoic acid, 4-hydroxyheptanoic acid, 4-hydroxyoctanoic acid, 4-hydroxynonanoic acid, 4-hydroxydecanoic acid, 4-hydroxyundecanoic acid, 4-hydroxydodecanoic acid, 4-hydroxytridecanoic acid, 4-hydroxytetradecanoic acid, 4-hydroxyhexadecanoic acid, and 4-hydroxyoctadecanoic acid.
[0026] Examples of P3HA include poly(3-hydroxybutyrate) (hereinafter, sometimes referred to as "P3HB"), which is a homopolymer of 3HB, poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (hereinafter, sometimes referred to as "P3HB3HH"), poly(3-hydroxybutyrate-co-4-hydroxybutyrate) (hereinafter, sometimes referred to as "P3HB4HB"), poly(3-hydroxybutyrate-co-3-hydroxypropionate), etc. As P3HA, only one type may be used, or two or more types may be used in combination. In this specification, "poly(X-co-Y)" refers to a copolymer containing X repeating units and Y repeating units, and is intended to mean a copolymer obtained by copolymerizing a monomer from which the X repeating unit is derived and a monomer from which the Y repeating unit is derived. In addition, during the production of P3HA by microorganisms, a small amount (approximately 1 mol % or less) of a monomer may be copolymerized. However, if this does not significantly affect the physical properties of the resulting P3HA, the monomer is considered to be uncopolymerized, and the product will be named without including that monomer.
[0027] P3HA can be produced by microorganisms. Such microbially produced P3HA is usually P3HA composed only of D-form (R-form) 3-hydroxyalkanoic acid repeating units. Among the microbially produced P3HA, P3HB, P3HB3HH and P3HB4HB are preferred, and P3HB3HH and P3HB4HB are more preferred, because they are easy to produce industrially.
[0028] It is also preferred that P3HA contains a 3-hydroxybutanoic acid (3HB) repeating unit. When P3HA contains a 3HB repeating unit, the composition ratio of the 3HB repeating unit in the total monomer repeating units (100 mol%) is preferably 60 mol% to 99 mol%, more preferably 61 mol% to 97 mol%, and even more preferably 62 mol% to 95 mol%, from the viewpoint of the balance between flexibility and strength. When the composition ratio of the 3HB repeating unit in P3HA is 60 mol% or more, there is an advantage that the rigidity of the crosslinked resin particles can be further improved. On the other hand, when the composition ratio of the 3HB repeating unit in P3HA is 99 mol% or less, there is an advantage that the flexibility of the crosslinked resin particles tends to be further improved. The monomer composition ratio of P3HA can be measured by gas chromatography or the like (for example, see International Publication No. 2014 / 020838). As P3HA, two or more types having different composition ratios of the 3HB repeating unit may be used in combination.
[0029] Microorganisms that produce P3HA are not particularly limited as long as they have the ability to produce P3HA. For example, the first P3HB-producing bacterium was Bacillus megaterium, discovered in 1925, and other natural microorganisms such as Cupriavidus necator (formerly classified as Alcaligenes eutrophus and Ralstonia eutropha) and Alcaligenes latus are also known. In these microorganisms, P3HB accumulates within the bacterial cells.
[0030] Also, as producers of copolymers of 3HB and other hydroxyalkanoic acids, Aeromonas caviae, which produces P3HB3HH, and Alcaligenes eutrophus, which produces poly(3-hydroxybutyrate-co-4-hydroxybutyrate), are known. In particular, in order to increase the productivity of P3HB3HH, Alcaligenes eutrophus AC32 (FERM BP-6038) (T. Fukui, Y. Doi, J. Bateriol., 179, p4821-4830 (1997)) into which genes of P3HA synthase group have been introduced is preferred. Microorganisms that have been cultured under appropriate conditions to accumulate P3HA in the cells are used. In addition to the above, genetically modified microorganisms into which various P3HA synthesis-related genes have been introduced may be used depending on the P3HA to be produced, and culture conditions, including the type of substrate, may be optimized.
[0031] The weight average molecular weight of the PHA is not particularly limited. The weight average molecular weight of the PHA is preferably 50,000 to 3,000,000, preferably 100,000 to 2,000,000, and more preferably 150,000 to 1,500,000. When the weight average molecular weight of the PHA is 50,000 or more, it has an advantage that the tendency of the strength of the crosslinked resin particles to decrease can be reduced or avoided. Also / alternatively, when the weight average molecular weight of the PHA is 50,000 or more, it has an advantage that the tendency of the low molecular weight component to become sticky can be reduced or avoided. On the other hand, a PHA having a weight average molecular weight of 3,000,000 or less can have an advantage that the PHA is easy to manufacture and / or that the PHA is easy to handle in order to achieve the object of one embodiment of the present invention. The numerical value of the weight average molecular weight of the PHA is a value obtained by measuring the PHA before the crosslinking treatment.
[0032] The weight average molecular weight can be measured by using gel permeation chromatography (GPC) (Shimadzu Corporation's "High Performance Liquid Chromatograph 20A System"), polystyrene gel (Showa Denko KK's "KG 4A", "K-806M", etc.) as a column, and chloroform as a mobile phase. The weight average molecular weight can be determined as a molecular weight converted into polystyrene using a calibration curve obtained by measuring polystyrene with a known molecular weight by the same measurement method. In this case, the calibration curve can be created using polystyrene with weight average molecular weights of 31,400, 197,000, 668,000, and 1,920,000. As the column for the GPC, a column appropriate for measuring the molecular weight may be used.
[0033] The PHA content in the present crosslinked resin particles is not particularly limited, but is preferably 50% by weight or more, more preferably 60% by weight or more, even more preferably 70% by weight or more, even more preferably 80% by weight or more, particularly preferably 90% by weight or more, and may be 100% by weight, based on the total amount of the present crosslinked resin particles (100% by weight).
[0034] (Aliphatic polyester other than PHA) The crosslinked resin particles of the present invention may contain, in addition to PHA, an aliphatic polyester other than PHA. Aliphatic polyesters other than PHA are also generally biodegradable resins.
[0035] Examples of the aliphatic polyester other than PHA include (i) polycaprolactone (PCL), (ii) polylactic acid (PLA), and (iii) aliphatic polyester having a structure obtained by polycondensation of an aliphatic diol and an aliphatic dicarboxylic acid.
[0036] In this specification, "polylactic acid" refers to a compound having a repeating monomer unit of [-CHCH 3 The term "polylactic acid" refers to a resin that contains 50 mol % or more of repeating units represented by the formula [-CHCH 3The repeating units represented by the formula: --CO-O-- may account for 60 mol % or more, 70 mol % or more, 80 mol % or more, or 90 mol % or more of all monomer repeating units (100 mol %).
[0037] As the polylactic acid, a conventionally known polylactic acid can be used. The polylactic acid may be crystalline polylactic acid, amorphous polylactic acid, or a mixture of crystalline polylactic acid and amorphous polylactic acid.
[0038] The polylactic acid may be a homopolymer of lactic acid, a copolymer of lactic acid and other monomers, or a blend of a homopolymer of lactic acid and a copolymer of lactic acid and other monomers.
[0039] Examples of the other monomers include aliphatic hydroxycarboxylic acids other than lactic acid, aliphatic polyhydric alcohols, aliphatic polycarboxylic acids, polyfunctional polysaccharides, and caprolactone.
[0040] The lactic acid raw material for producing polylactic acid is not particularly limited, and L-lactic acid, D-lactic acid, DL-lactic acid, or a mixture thereof, or L-lactide, D-lactide, meso-lactide, or a mixture thereof, etc. Lactic acid obtained by microbial fermentation from renewable raw materials derived from plants such as starch can be suitably used.
[0041] The method for producing polylactic acid is not particularly limited, and known methods such as dehydration condensation polymerization and ring-opening polymerization can be used.
[0042] The weight-average molecular weight of polylactic acid is not particularly limited, but is preferably 50,000 to 1,000,000, more preferably 70,000 to 700,000, and even more preferably 100,000 to 400,000. When the weight-average molecular weight of polylactic acid is 50,000 or more, the crosslinked resin particles, and the crosslinked resin particles and their molded bodies can obtain sufficient rigidity and / or strength. On the other hand, polylactic acid having a weight-average molecular weight of 1,000,000 or less can have the advantage that the polylactic acid is easy to produce and / or easy to handle in order to achieve the object of one embodiment of the present invention.
[0043] "Polycaprolactone" includes, but is not limited to, polymers obtained by ring-opening polymerization of ε-caprolactone. In one embodiment of the present invention, PCL obtained by other manufacturing methods can also be used. An organometallic catalyst can also be used to promote the polymerization of PCL. In this specification, "PCL" also includes copolymers of ε-caprolactone and monomers other than ε-caprolactone (e.g., lactide, glycolic acid, etc.).
[0044] PCL typically has a melting point of 50°C to 65°C, a crystallization temperature of 10°C to 30°C, and a glass transition point of -50°C to -60°C.
[0045] The weight-average molecular weight of PCL is preferably 30,000 to 500,000, more preferably 100,000 to 400,000. When the weight-average molecular weight of PCL is 30,000 or more, the present crosslinked resin particles, the crosslinked resin particles, and their molded articles can have sufficient rigidity and / or strength. When the weight-average molecular weight of PCL is 500,000 or less, there is an advantage that the present crosslinked resin particles can be easily processed.
[0046] Commercially available PCL products include, for example, Ingevity's "Capa6506" (powder, Mw=130,000), "Capa6500" (pellet, Mw=130,000), "Capa6806" (powder, Mw=230,000), "Capa6800" (pellet, Mw=230,000), and "FB100" (pellet, Mw=300,000, contains PCL crosslinked material). Specific examples of the aliphatic polyester having a structure formed by polycondensation of the aliphatic diol and the aliphatic dicarboxylic acid include polyethylene succinate, polybutylene succinate (hereinafter sometimes referred to as "PBS"), polyhexamethylene succinate, polyethylene adipate, polybutylene adipate, polyhexamethylene adipate, polybutylene succinate adipate (hereinafter sometimes referred to as "PBSA"), polyethylene sebacate, polybutylene sebacate, and the like.
[0047] In this specification, "PBS" refers to an aliphatic polyester copolymer synthesized by an esterification reaction and / or transesterification reaction, and a condensation polymerization reaction, between an aliphatic diol component mainly composed of 1,4-butanediol and an aliphatic dicarboxylic acid component mainly composed of a succinic acid component such as succinic acid and / or its derivatives.
[0048] PBS is, for example, [-CO-(CH 2 ) 2 -CO-O-(CH 2 ) 4 -O-].
[0049] PBS can be produced from petroleum or from non-petroleum-based materials (e.g., plants).
[0050] In this specification, "PBS" also includes a "PBS-based resin" which is a copolymer of the above-mentioned PBS with a monomer other than 1,4-butanediol and succinic acid (e.g., L-lactic acid and / or caprolactone).
[0051] Commercially available PBS can also be used, such as "BioPBS FZ71" and "BioPBS FZ91" manufactured by Mitsubishi Chemical Corporation.
[0052] In this specification, "PBSA" refers to an aliphatic polyester copolymer synthesized by an esterification reaction and a condensation polymerization reaction between an aliphatic diol component mainly composed of 1,4-butanediol, an aliphatic dicarboxylic acid component mainly composed of a succinic acid component such as succinic acid and / or its derivatives, and adipic acid.
[0053] As long as the effect of one embodiment of the present invention is achieved, PBSA may have, in addition to butanediol repeating units, succinic acid repeating units, and adipic acid repeating units, any diol repeating units other than butanediol, any dicarboxylic acid repeating units other than succinic acid and adipic acid, and / or hydroxyalkanoic acid repeating units. Examples of the optional diols include ethylene glycol, 1,3-propanediol, 1,2-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanediol, and 1,4-cyclohexanedimethanol. Examples of the optional dicarboxylic acids include suberic acid, sebacic acid, dodecanoic acid, succinic anhydride, and adipic anhydride.
[0054] In this specification, "PBSA" also includes "PBSA-based resins" which are copolymers of the above-mentioned PBSA with monomers other than 1,4-butanediol, succinic acid, and adipic acid (e.g., lactic acid, terephthalic acid, malic acid, sebacic acid, azelaic acid, etc.) within the scope that does not impair biodegradability.
[0055] Commercially available PBSA can also be used, such as "BioPBS FD72" and "BioPBS FD92" manufactured by Mitsubishi Chemical Corporation.
[0056] As the aliphatic polyester, one of the above-mentioned various resins may be used alone, or two or more of them may be used in combination. In addition, among the above-mentioned various resins, one of the above-mentioned resins may be used alone, or two or more of them may be used in combination.
[0057] (Aliphatic polyester other than PHA) The crosslinked resin particles may contain an aliphatic-aromatic polyester in addition to a PHA. The aliphatic-aromatic polyester is also generally a biodegradable resin.
[0058] Examples of the aliphatic aromatic polyester include aliphatic aromatic polyesters obtained using both an aliphatic compound and an aromatic compound as monomers (using both an aliphatic compound and an aromatic compound as monomers).
[0059] Examples of the aliphatic aromatic polyester include polybutylene adipate terephthalate (hereinafter sometimes referred to as "PBAT"), polybutylene sebacate terephthalate (hereinafter sometimes referred to as "PBSeT"), polybutylene azelate terephthalate (hereinafter sometimes referred to as "PBAzT"), polybutylene succinate terephthalate (hereinafter sometimes referred to as "PBST"), polybutylene succinate adipate terephthalate (hereinafter sometimes referred to as "PBSAT"), and the like.
[0060] As used herein, "PBAT" refers to a random copolymer of 1,4-butanediol with adipic acid and terephthalic acid.
[0061] The PBAT is not particularly limited, but a PBAT obtained by reacting (a) a mixture consisting essentially of 35 to 95 mol % of adipic acid or an ester-forming derivative thereof, or a mixture of these, and 5 to 65 mol % of terephthalic acid or an ester-forming derivative thereof, or a mixture of these (the sum of the individual mol % is 100 mol %), with (b) a mixture containing butanediol (wherein the molar ratio of (a) to (b) is 0.4:1 to 1.5:1), as described in JP-A-10-508640 and the like, is preferred.
[0062] In one embodiment of the present invention, instead of the 1,4-butanediol in the production of PBAT, glycol compounds such as ethylene glycol, propylene glycol, heptanediol, hexanediol, octanediol, nonanediol, decanediol, 1,4-cyclohexanedimethanol, neopentyl glycol, glycerin, pentaerythritol, bisphenol A, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, etc. Also, in one embodiment of the present invention, instead of the adipic acid in the production of PBAT, dicarboxylic acids such as oxalic acid, succinic acid, azelaic acid, dodecanedioic acid, malonic acid, glutaric acid, cyclohexanedicarboxylic acid, terephthalic acid, isophthalic acid, phthalic acid, naphthalenedicarboxylic acid, bis(p-carboxyphenyl)methane, anthracenedicarboxylic acid, 4,4'-diphenyletherdicarboxylic acid, 5-sodium sulfoisophthalic acid, 5-tetrabutylphosphonium isophthalic acid, etc. may be used.
[0063] Commercially available PBAT can also be used, for example, "Ecoflex C1200" manufactured by BASF.
[0064] In this specification, "PBSeT" refers to a random copolymer of 1,4-butanediol, sebacic acid, and terephthalic acid. For each embodiment of PBSeT, the above embodiment of PBAT may be appropriately applied in which the portions "adipic acid" and "adipic acid or an ester-forming derivative thereof" are replaced with "sebacic acid" and "sebacic acid or an ester-forming derivative thereof," respectively.
[0065] Commercially available PBSeT can also be used. Examples of commercially available PBSeT include "Ecoflex FS blend C2200" (registered trademark) manufactured by BASF.
[0066] In this specification, "PBAzT" refers to a random copolymer of 1,4-butanediol, azelaic acid, and terephthalic acid. For each embodiment related to PBAzT, the above embodiment related to PBAT in which "adipic acid" and "adipic acid or an ester-forming derivative thereof" are replaced with "azelaic acid" and "azelaic acid or an ester-forming derivative thereof", respectively, can be appropriately used.
[0067] In this specification, "PBST" refers to the above-mentioned PBS into which a terephthalate unit has been introduced. More specifically, "PBST" refers to an aliphatic aromatic polyester copolymer synthesized by an esterification reaction between an aliphatic dicarboxylic acid component mainly composed of a succinic acid component such as succinic acid and / or its derivatives and terephthalic acid, and a condensation polymerization reaction.
[0068] In the present specification, "PBSAT" means a copolymer containing, among the aliphatic dicarboxylic acid residues, the residues of succinic acid:adipic acid:phthalic acid, preferably in a ratio of 70-90:5-15:5-15 mol %. Therefore, in order to produce PBSAT, for example, a method can be mentioned in which a dicarboxylic acid mixture containing succinic acid, adipic acid, and phthalic acid in the above ratio is esterified with 1,4-butanediol, an aliphatic glycol, in a molar ratio of 1:1.2-2.0, and then a condensation polymerization reaction is carried out. The reactive groups and reaction conditions used in the reaction can be appropriately adopted from those used in existing biodegradable resins such as PBS.
[0069] As the aliphatic aromatic polyester, one of the above-mentioned various resins may be used alone, or two or more of them may be used in combination. In addition, among the above-mentioned various resins, one of the above-mentioned resins may be used alone, or two or more of them may be used in combination.
[0070] When the crosslinked resin particles contain an aliphatic polyester other than PHA or an aliphatic aromatic polyester, the aliphatic polyester other than PHA and the aliphatic aromatic polyester may have a crosslinked structure or may not have a crosslinked structure. A crosslinked structure may be formed between the PHA and the aliphatic polyester and / or the aliphatic aromatic polyester other than PHA. That is, in this specification, the term "PHA having a crosslinked structure" is a concept that includes not only PHA having a structure in which molecular chains of PHA are bonded to each other, but also a molecule having a structure in which PHA and a molecule other than PHA (for example, aliphatic polyester and / or aliphatic aromatic polyester other than PHA) are bonded.
[0071] (Peroxide) The crosslinked structure of the PHA contained in the crosslinked resin particles is not particularly limited, but is preferably crosslinked using a peroxide. That is, the crosslinked resin particles preferably contain a PHA crosslinked using a peroxide. When a peroxide is used, radicals generated by decomposition of the peroxide act on the molecules of the resin (especially PHA) constituting the resin particles. This allows the molecular chains of the resin constituting the resin particles to be directly bonded to each other, forming a crosslinked structure.
[0072] When the crosslinked resin particles contain PHA crosslinked with peroxide, the aqueous dispersion containing the crosslinked resin particles may contain substances derived from the peroxide used to introduce the crosslinked structure (such as decomposition products of the peroxide and unreacted peroxide). Alternatively, when the crosslinked resin particles contain PHA crosslinked with peroxide, substances derived from the peroxide used to introduce the crosslinked structure (such as decomposition products of the peroxide and unreacted peroxide) may be attached to the surface of the obtained crosslinked resin particles. That is, when the crosslinked resin particles contain PHA crosslinked with peroxide, the crosslinked resin particles may contain substances derived from the peroxide (such as decomposition products of the peroxide and unreacted peroxide). In other words, when the crosslinked resin particles contain substances derived from peroxide, it can be said that the crosslinked resin particles are crosslinked resin particles containing PHA crosslinked with peroxide. Therefore, by analyzing the content of substances derived from peroxide in the crosslinked resin particles, it is possible to determine whether the crosslinked resin particles contain PHA crosslinked with peroxide (that is, whether they are crosslinked resin particles or uncrosslinked resin particles).
[0073] The peroxide may be an organic peroxide or an inorganic peroxide. The peroxide is preferably an organic peroxide because it can increase the gel fraction more efficiently.
[0074] As the organic peroxide, it is preferable to use at least one selected from the group consisting of diacyl peroxides, alkyl peroxy esters, dialkyl peroxides, hydroperoxides, peroxy ketals, peroxy carbonates, and peroxy dicarbonates, taking into consideration the heating temperature and / or time during the crosslinking treatment.
[0075] Specific examples of such organic peroxides include butyl peroxy neododecanoate, octanoyl peroxide, dilauroyl peroxide, succinic peroxide, a mixture of toluoyl peroxide and benzoyl peroxide, benzoyl peroxide, bis(butylperoxy)trimethylcyclohexane, butylperoxylaurate, dimethyldi(benzoylperoxy)hexane, bis(butylperoxy)methylcyclohexane, bis(butylperoxy)cyclohexane, and butylperoxybenzo. ester, butyl bis(butylperoxy)valerate, dicumyl peroxide, di-t-hexyl peroxide, t-butylperoxy 2-ethylhexanoate, t-butylperoxyisobutyrate, t-butylperoxypivalate, t-hexylperoxypivalate, t-butylperoxymethyl monocarbonate, t-pentylperoxymethyl monocarbonate, t-hexylperoxymethyl monocarbonate, t-heptylperoxymethyl monocarbonate, t-octylperoxymethyl monocarbonate, 1 ,1,3,3-tetramethylbutylperoxymethyl monocarbonate, t-butylperoxyethyl monocarbonate, t-pentylperoxyethyl monocarbonate, t-hexylperoxyethyl monocarbonate, t-heptylperoxyethyl monocarbonate, t-octylperoxyethyl monocarbonate, 1,1,3,3-tetramethylbutylperoxyethyl monocarbonate, t-butylperoxy n-propyl monocarbonate, t-pentylperoxy n-propyl monocarbonate, t-hexylperoxyethyl monocarbonate peroxy n-propyl monocarbonate, t-heptyl peroxy n-propyl monocarbonate, t-octyl peroxy n-propyl monocarbonate, 1,1,3,3-tetramethylbutyl peroxy n-propyl monocarbonate, t-butyl peroxy isopropyl monocarbonate, t-pentyl peroxy isopropyl monocarbonate, t-hexyl peroxy isopropyl monocarbonate, t-heptyl peroxy isopropyl monocarbonate, t-octyl peroxy isopropyl monocarbonate, 1,1,3,3-Tetramethylbutylperoxyisopropyl monocarbonate, t-butylperoxyn-butyl monocarbonate, t-pentylperoxyn-butyl monocarbonate, t-hexylperoxyn-butyl monocarbonate, t-heptylperoxyn-butyl monocarbonate, t-octylperoxyn-butyl monocarbonate, 1,1,3,3-tetramethylbutylperoxyn-butyl monocarbonate, t-butylperoxyisobutyl monocarbonate, t-pentylperoxyisobutyl monocarbonate, t -Hexylperoxyisobutylmonocarbonate, t-heptylperoxyisobutylmonocarbonate, t-octylperoxyisobutylmonocarbonate, 1,1,3,3-tetramethylbutylperoxyisobutylmonocarbonate, t-butylperoxysec-butylmonocarbonate, t-pentylperoxysec-butylmonocarbonate, t-hexylperoxysec-butylmonocarbonate, t-heptylperoxysec-butylmonocarbonate, t-octylperoxysec-butylmonocarbonate peroxy t-butyl monocarbonate, 1,1,3,3-tetramethylbutylperoxy sec-butyl monocarbonate, t-butylperoxy t-butyl monocarbonate, t-pentylperoxy t-butyl monocarbonate, t-hexylperoxy t-butyl monocarbonate, t-heptylperoxy t-butyl monocarbonate, t-octylperoxy t-butyl monocarbonate, 1,1,3,3-tetramethylbutylperoxy t-butyl monocarbonate, t-butylperoxy 2-ethylhexyl monocarbonate, t-pentylperoxy 2-ethylhexyl monocarbonate, ethylhexyl monocarbonate, t-hexylperoxy 2-ethylhexyl monocarbonate, t-heptylperoxy 2-ethylhexyl monocarbonate, t-octylperoxy 2-ethylhexyl monocarbonate, 1,1,3,3-tetramethylbutylperoxy 2-ethylhexyl monocarbonate, diisobutyl peroxide, cumylperoxy neodecanoate, di-n-propylperoxydicarbonate, diisopropylperoxydicarbonate, di-sec-butylperoxydicarbonate, 1,1,3,3-Tetramethylbutylperoxyneodecanoate, bis(4-t-butylcyclohexyl)peroxydicarbonate, bis(2-ethylhexyl)peroxydicarbonate, t-hexylperoxyneodecanoate, t-butylperoxyneodecanoate, t-butylperoxyneoheptanoate, t-hexylperoxypivalate, t-butylperoxypivalate, di(3,5,5-trimethylhexanoyl)peroxide, dilauroyl peroxide, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, disuccinic acid peroxide, 2,5-dimethyl-2,5-bis(2-ethylhexanoylperoxy) Examples of organic peroxides include hexane, t-hexylperoxy-2-ethylhexanoate, di(4-methylbenzoyl)peroxide, dibenzoylperoxide, t-butylperoxy-2-ethylhexylcarbonate, t-butylperoxyisopropylcarbonate, 1,6-bis(t-butylperoxycarbonyloxy)hexane, t-butylperoxy-3,5,5-trimethylhexanoate, t-butylperoxyacetate, t-butylperoxybenzoate, t-amylperoxy, 3,5,5-trimethylhexanoate, 2,2-bis(4,4-di-t-butylperoxycyclohexyl)propane, and 2,2-di-t-butylperoxybutane. The organic peroxides may be used alone or in combination of two or more.
[0076] Among these, t-butylperoxyisopropyl monocarbonate, t-pentylperoxyisopropyl monocarbonate, t-hexylperoxyisopropyl monocarbonate, t-butylperoxy2-ethylhexyl monocarbonate, t-pentylperoxy2-ethylhexyl monocarbonate, t-hexylperoxy2-ethylhexyl monocarbonate, t-amylperoxyisopropyl monocarbonate, di-t-hexyl peroxide, t-butylperoxy2-ethylhexyl monocarbonate, Xanoate, t-butylperoxyisobutyrate, t-hexylperoxy 2-ethylhexanoate, 1,1,3,3-tetramethylbutylperoxy 2-ethylhexanoate, t-butylperoxypivalate, t-hexylperoxypivalate, t-butylperoxyneodecanoate, t-hexylperoxyneodecanoate, and 1,1,3,3-tetramethylbutylperoxyneodecanoate are preferred organic peroxides because they can efficiently promote crosslinking of PHA.
[0077] Since the heating temperature during crosslinking treatment can be set low, the peroxide is preferably a compound exhibiting a one-hour half-life temperature of 200° C. or less, more preferably a compound exhibiting a one-hour half-life temperature of 170° C. or less, and even more preferably a compound exhibiting a one-hour half-life temperature of 140° C. or less. The lower limit of the one-hour half-life temperature of the peroxide may be 50° C. or more, 60° C. or more, or 70° C. or more.
[0078] Particularly preferred organic peroxides exhibiting such a one-hour half-life temperature are t-butylperoxyisopropylmonocarbonate, t-butylperoxy2-ethylhexylmonocarbonate, di-sec-butylperoxydicarbonate, t-butylperoxy2-ethylhexanoate, t-butylperoxyisobutyrate, t-hexylperoxy2-ethylhexanoate, 1,1,3,3-tetramethylbutylperoxy2-ethylhexanoate, t-butylperoxypivalate, t-hexylperoxypivalate, t-butylperoxyneodecanoate, t-hexylperoxyneodecanoate, and 1,1,3,3-tetramethylbutylperoxyneodecanoate.
[0079] The case where the peroxide is an inorganic peroxide will be described. Examples of the inorganic peroxide include hydrogen peroxide, potassium peroxide, calcium peroxide, sodium peroxide, magnesium peroxide, potassium persulfate, sodium persulfate, and ammonium persulfate, taking into consideration the heating temperature and / or time during crosslinking treatment. Among them, hydrogen peroxide, potassium persulfate, sodium persulfate, and ammonium persulfate are preferred in terms of ease of handling and having a decomposition temperature suitable for the heating temperature during crosslinking treatment. The inorganic peroxide may be used alone or in combination of two or more. An organic peroxide and an inorganic peroxide may be used in combination.
[0080] (polyfunctional compound) The crosslinked structure in the present crosslinked resin particle may be introduced by using only peroxide, or may be introduced by using both peroxide and polyfunctional compound.That is, the present crosslinked resin particle may be crosslinked by using peroxide and further polyfunctional compound.When using both peroxide and polyfunctional compound, it is possible to increase the gel fraction of the crosslinked resin particle with a smaller amount of peroxide compared to using only peroxide.
[0081] In this specification, the term "polyfunctional compound" refers to a compound having two or more functional groups (e.g., radical reactive groups) capable of bonding with PHA (hydroxyalkanoate unit) in one molecule. The polyfunctional compound is not particularly limited as long as it satisfies the above definition, but a compound having reactivity with a radical generated from a peroxide is preferred, and a compound having two or more radical reactive groups in one molecule is particularly preferred. The radical reactive group is preferably at least one selected from the group consisting of a vinyl group, an allyl group, an acryloyl group, and a methacryloyl group.
[0082] Such polyfunctional compounds are not particularly limited, but examples thereof include allyl (meth)acrylate, allyl alkyl (meth)acrylates, allyloxy alkyl (meth)acrylates, polyfunctional (meth)acrylates having two or more (meth)acrylic groups, such as ethylene glycol di(meth)acrylate, butanediol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and pentaerythritol (meth)acrylate, divinylbenzene, diallyl phthalate, triallyl cyanurate, triallyl isocyanurate, and divinylbenzene. Preferably, the compound is one or more selected from the group consisting of allyl methacrylate, triallyl isocyanurate, butanediol di(meth)acrylate, and divinylbenzene, and more preferably, the compound is one or more selected from the group consisting of allyl methacrylate and triallyl isocyanurate.
[0083] When a crosslinked structure is formed in the presence of a polyfunctional compound, the resulting crosslinked resin particles may generally contain a structure derived from the polyfunctional compound, in which case molecular chains of PHA are bonded to each other via the structure derived from the polyfunctional compound.
[0084] (Protein content) The present crosslinked resin particles are crosslinked resin particles having a protein content of 200 to 20,000 ppm. Because of this constitution, the present crosslinked resin particles can be mixed with a thermoplastic resin to provide a resin composition and a molded article having excellent mechanical properties such as impact strength and good color tone. From the above viewpoints, the protein content of the present crosslinked resin particles is 200 to 20,000 ppm, preferably 300 to 15,000 ppm, more preferably 500 to 10,000 ppm, and even more preferably 800 to 5,000 ppm. The protein content of the crosslinked resin particles can be measured by using a BCA Protein Assay Kit (manufactured by Thermo Fisher Scientific) for an aqueous dispersion of the crosslinked resin particles.
[0085] In addition, the "protein content" measured by the above method may include not only the protein present on the surface of the target crosslinked resin particles, but also the amount of protein present in the aqueous dispersion away from the crosslinked resin particles. In this specification, the total value of all of these is referred to as the "protein content" of the target crosslinked resin particles.
[0086] (Gel fraction) In this specification, the amount of crosslinked structures in the resin in the crosslinked resin particles (PHA in the present crosslinked resin particles) affects the gel fraction of the crosslinked resin particles. In other words, the amount of crosslinked structures in the resin in the crosslinked resin particles can be evaluated by the gel fraction of the crosslinked resin particles. Specifically, the more crosslinked structures the resin in the crosslinked resin particles has, the higher the gel fraction of the crosslinked resin particles. The present crosslinked resin particles contain a certain amount or more of PHA having a crosslinked structure, and therefore exhibit a high gel fraction, specifically a gel fraction of 50% or more. Since the present crosslinked resin particles have a gel fraction of 50% or more, the crosslinked resin particles have excellent hardness, heat resistance, and solvent resistance.
[0087] The value of the gel fraction is 50% or more, preferably 60% or more, more preferably 70% or more, even more preferably 75% or more, and particularly preferably 80% or more. It may also be 85% or more, or 90% or more. The upper limit of the gel fraction is not particularly limited, and may be 100% or less. From the viewpoint of production efficiency of crosslinked resin particles, the upper limit of the gel fraction is preferably 99.5% or less, more preferably 99% or less. The upper limit of the gel fraction may also be 98% or less, 97% or less, or 96% or less.
[0088] The gel fraction is a value measured as follows: (1) A dried product of the crosslinked resin particles is added to chloroform so as to give a concentration of 0.7% by weight, and the resulting mixture is reacted at 60°C for 30 minutes to obtain a chloroform solution; (2) After that, the chloroform solution is allowed to stand at room temperature for 3 hours, and then the chloroform solution is filtered through a membrane filter having a pore size of 0.45 μm; (3) The gel remaining on the filter is dried, and the weight of the dried gel together with the filter is measured, and the gel fraction is calculated using the following formula. Formula: gel fraction (%)={(weight of filter including dried gel−weight of filter only) / weight of dried crosslinked resin particles used in measurement}×100.
[0089] (Volume average particle size) The crosslinked resin particles preferably have a volume average particle diameter of 0.1 μm to 10 μm. This configuration allows the crosslinked resin particles to be suitably used in various applications as described below. From the viewpoint of practical use, the lower limit of the volume average particle diameter is more preferably 0.3 μm or more, and even more preferably 0.5 μm or more. Moreover, from the viewpoint of productivity (production of PHA and / or crosslinking treatment, etc.), the upper limit of the volume average particle diameter is more preferably 8 μm or less, and even more preferably 5 μm or less.
[0090] In this specification, the volume average particle diameter (MV) of the crosslinked resin particles is a value obtained by measuring an aqueous dispersion liquid in which the crosslinked resin particles are dispersed in an aqueous medium. More specifically, the volume average particle diameter (MV) of the crosslinked resin particles is a value calculated by the following formula (1), i.e., formula (2), when the particle diameters of the individual crosslinked resin particles contained in a group of k total crosslinked resin particles are d1, d2,...di...dk in ascending order, and the volumes of the individual crosslinked resin particles are v1, v2,...vi...vk (here, the volume of the crosslinked resin particles with particle diameter di is Vi).
[0091]
number
[0092] In addition, a general-purpose measuring device can be used as a device for measuring the volume average particle diameter of the crosslinked resin particles in the aqueous dispersion (in other words, the particle diameter and volume of the crosslinked resin particles), and an example of such a device is MicrotracMT3300EXII manufactured by Nikkiso Co., Ltd. In addition, in this specification, the volume average particle diameter of the uncrosslinked resin particles can be measured by replacing "crosslinked resin particles" with "uncrosslinked resin particles" in the above method.
[0093] (others) The crosslinked resin particles of the present invention may be those whose crosslinked structure is composed only of PHA, or may further contain a component other than PHA having a crosslinked structure. Examples of the component other than PHA having a crosslinked structure include aliphatic polyester resins other than PHA (including aliphatic aromatic polyesters), resins other than biodegradable resins, antioxidants, hydrolysis inhibitors, antiblocking agents, crystal nucleating agents, lubricants, ultraviolet absorbers, etc.
[0094] The present crosslinked resin particles are different from the expanded resin particles disclosed in WO 2007 / 049694 and WO 2019 / 146555, and are preferably not expanded. In other words, the present crosslinked resin particles are preferably substantially free of air bubbles inside the particles. "Substantially free of air bubbles inside the particles" means that the volume of air bubbles (spaces) is 10% or less of the volume of the crosslinked resin particles (100%).
[0095] When the crosslinked resin particles are not expanded, the apparent density of the crosslinked resin particles is relatively large. The apparent density of the crosslinked resin particles is 0.6 g / cm. 3 It is preferable that the density exceeds 0.7 g / cm 3 More preferably, it is 0.9 g / cm or more. 3 The apparent density of the crosslinked resin particles can be determined by the method described in JIS K0061 (Method for measuring density and specific gravity of chemical products) or JIS Z8807 (Method for measuring density and specific gravity of solids).
[0096] The average weight per particle of the present crosslinked resin particles is not particularly limited. For example, when the volume average particle size of the crosslinked resin particles is 10 μm or less, the average weight per particle of the crosslinked resin particles can be much less than 0.1 mg.
[0097] The crosslinked resin particles may be dried. The shape of the dried particles may be, but is not limited to, a powder, pellet, crumb, film, sheet, or other shape depending on the drying method.
[0098] (Aqueous dispersion) In another embodiment of the present invention, an aqueous dispersion is provided in which the crosslinked resin particles are dispersed in an aqueous medium.
[0099] The aqueous medium contained in the aqueous dispersion may be water alone or may be a mixed solvent of water and a water-compatible organic solvent. In the mixed solvent, the concentration of the water-compatible organic solvent is not particularly limited as long as it is equal to or lower than the solubility in water of the organic solvent used.
[0100] The organic solvent is not particularly limited, but examples thereof include alcohols such as methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, isobutanol, pentanol, hexanol, and heptanol; ketones such as acetone and methyl ethyl ketone; ethers such as tetrahydrofuran and dioxane; nitriles such as acetonitrile and propionitrile; amides such as dimethylformamide and acetamide; dimethyl sulfoxide; pyridine; piperidine; and the like. Among them, methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, isobutanol, acetone, methyl ethyl ketone, tetrahydrofuran, dioxane, acetonitrile, propionitrile, and the like are preferred because they are easily removed. Moreover, methanol, ethanol, 1-propanol, 2-propanol, butanol, acetone, and the like are more preferred because they are easily available. Furthermore, methanol, ethanol, and acetone are particularly preferred.
[0101] The water content in the entire aqueous medium (100% by weight) constituting the aqueous dispersion is preferably 5% by weight to 100% by weight. The water content in 100% by weight of the aqueous medium is more preferably 10% by weight or more, more preferably 30% by weight or more, even more preferably 50% by weight or more, and particularly preferably 70% by weight or more. The water content in 100% by weight of the aqueous medium may be 90% by weight or more, or may be 95% by weight or more.
[0102] The concentration of the crosslinked resin particles in the aqueous dispersion is not particularly limited, and may be, for example, 1% by weight to 60% by weight. The aqueous dispersion may contain a dispersant, which will be described later.
[0103] (Applications of crosslinked resin particles) The use of the present crosslinked resin particles (and the aqueous dispersion containing the present crosslinked resin particles) is not particularly limited, and can be used in applications where conventionally known crosslinked resin particles are used. Specific examples include resin modifiers, rheology adjusters for paints or adhesives, paint pigments, paper coating agents, matting agents, antiblocking agents, cosmetic additives, toner additives, spacers for liquid crystals, coating agents, fillers for adhesive tapes, fiber processing agents, medical diagnostic test particles, fillers, aqueous coating films, coated paper, resin tubes, foamed particles, packaging materials, containers, cosmetic containers, antifouling resin compositions, heat seal paper, handle moldings, forks, films, resin films for twist packaging materials, bags, gloves, binding materials, multilayer films, stretched films, fibers, multifilaments, meltblown nonwoven fabrics, masks, pile fabrics, coffee filters, inflation moldings, blow moldings, calendar sheet moldings, injection moldings, laminates, films, sheets, etc. The uses of the present crosslinked resin particles are not limited to these.
[0104] 2. Method for Producing Crosslinked Resin Particles An example of a method for producing the present crosslinked resin particles will be specifically described. The present crosslinked resin particles can be produced by crosslinking molecular chains of PHA in PHA particles in an aqueous dispersion containing PHA particles before crosslinking treatment and peroxide, preferably by crosslinking molecular chains of PHA in PHA particles in a state where an aqueous dispersion of resin particles containing peroxide is heated to a temperature suitable for decomposing the peroxide. In this specification, the term "resin particles" refers to particles composed of a resin component that essentially constitutes the crosslinked resin particles (PHA in the case of the present crosslinked resin particles), and particularly refers to particles composed of a resin component made of an uncrosslinked resin. When the resin component contains 50% by weight or more of PHA, the resin particles can also be called PHA particles.
[0105] Specifically, the present method for producing crosslinked resin particles preferably includes a preparation step (1) of preparing an aqueous dispersion containing PHA particles having a protein content of 200 to 20,000 ppm, an impregnation step (2) of adding a peroxide to the aqueous dispersion of PHA particles to impregnate the PHA particles with the peroxide, and a crosslinking step (3) of heating the aqueous dispersion of PHA particles impregnated with the peroxide to a heating temperature to crosslink the molecular chains of the resin (e.g., molecular chains of PHA).More preferably, the present method for producing crosslinked resin particles further includes a maintenance step (4) of maintaining the heating temperature after all the peroxide has been added. That is, in one embodiment of the present invention, there is provided a method for producing crosslinked resin particles which contains a PHA having a crosslinked structure and has a gel fraction of 50% or more, the method comprising the steps of: a preparation step of preparing an aqueous dispersion containing PHA particles having a protein content of 200 to 20,000 ppm; an impregnation step of adding a peroxide to the aqueous dispersion of PHA particles to impregnate the PHA particles with the peroxide; and a crosslinking step of heating the aqueous dispersion of resin particles impregnated with the peroxide to a heating temperature to crosslink molecular chains of the PHA.
[0106] In this specification, the "method for producing crosslinked resin particles according to one embodiment of the present invention" may be referred to as the "present production method." The present production method can be suitably used as the method for producing the present crosslinked resin particles.
[0107] Each step that may be included in this production method will be described in detail below.
[0108] <Preparation process> The present production method includes a preparation step of preparing an aqueous dispersion containing PHA particles having a protein content of 200 to 20,000 ppm (hereinafter, may be referred to as "aqueous dispersion"). The preparation step is not particularly limited as long as it can prepare an aqueous dispersion containing PHA particles having a protein content of 200 to 20,000 ppm. The preparation step may be, for example, a step of preparing a mixture containing an aqueous medium and PHA particles.
[0109] In the preparation step, the aqueous dispersion of PHA particles can be prepared (prepared) by, for example, culturing a PHA-producing microorganism to accumulate PHA in the cells, then disrupting the cells in the culture solution to separate and remove the cell components, or by concentrating or diluting the aqueous dispersion. According to such a method, the process from producing PHA particles by culturing a PHA-producing microorganism to crosslinking treatment can be carried out without separating the PHA particles from water.
[0110] In the preparation step, when the aqueous dispersion is prepared using PHA-producing microorganisms as raw materials, the PHA particles in the aqueous dispersion contain impurities derived from the PHA-producing microorganisms, particularly proteins derived from the PHA-producing microorganisms. In this case, in order to make the protein content of the PHA particles in the obtained aqueous dispersion 200 to 20,000 ppm, it is preferable to carry out a step of adjusting the protein content of the PHA particles in the obtained aqueous dispersion to 200 to 20,000 ppm (protein amount adjustment step). By adjusting the protein content of the PHA particles to the above range, it is possible to carry out crosslinking of PHA while ensuring aggregation stability in the subsequent crosslinking step.
[0111] The protein content of the PHA particles in the aqueous dispersion obtained in the preparation step is basically the protein content of the crosslinked resin particles finally obtained. Therefore, from the viewpoint of providing crosslinked resin particles with a desired protein content, the protein content of the PHA particles in the aqueous dispersion obtained in the preparation step is 200 to 20,000 ppm, preferably 300 to 15,000 ppm, more preferably 500 to 10,000 ppm, and even more preferably 800 to 5,000 ppm. In this specification, the protein content of the PHA particles in the aqueous dispersion is a value measured by using a BCA Protein Assay Kit (manufactured by Thermo Fisher Scientific) for the aqueous dispersion, and specifically, a value measured by the method described in the Examples.
[0112] In the protein amount adjustment process, the method of adjusting the protein content of the PHA particles is not particularly limited, but a method of adding a protease to the aqueous dispersion precursor, in other words, a method of utilizing the enzyme reaction of the protease, is preferred.When a protease is used in the protein adjustment process, in order to prevent excessive protein decomposition, it is preferred to remove the protease after the reaction by washing immediately after the end of the enzyme reaction, or to inactivate the protease by adjusting the temperature or pH.In addition, in such a washing operation, a surfactant may be added before washing to increase the efficiency of protein removal.
[0113] In the protein amount adjustment step, when a protease is used, it is preferable to adjust the pH of the aqueous dispersion precursor to a pH near the optimum pH of the protease used, and it is preferable to adjust the temperature of the aqueous dispersion to a pH near the optimum temperature of the protease used. The amount of the protease added varies depending on the type of protease used, and cannot be generally specified, but is preferably 0.01% by weight to 2% by weight, and more preferably 0.03% by weight to 1% by weight, relative to a concentration of 100% by weight of the PHA particles. The time for reacting the protease is not particularly limited, but may be, for example, 30 minutes to 10 hours, or 1 hour to 5 hours. The temperature for reacting the protease is not particularly limited, and may be appropriately adjusted according to the optimum temperature of the protease used, but may be, for example, 20°C to 70°C, or 30°C to 60°C.
[0114] The proteolytic enzyme that can be used in the protein amount adjustment step is not particularly limited, but examples thereof include esperase, alcalase, pepsin, trypsin, papain, chymotrypsin, aminopeptidase, carboxypeptidase, and the like.
[0115] In addition to the above-mentioned method, in the preparation step, the dried PHA particles (e.g., powder) may be dispersed in an aqueous medium such as water to prepare an aqueous dispersion. In this case, it is preferable to use the PHA particles whose protein content has been adjusted to the above-mentioned range in advance. Alternatively, the PHA particles may be dispersed in an aqueous medium, and then the protein content of the PHA particles may be adjusted by the above-mentioned method.
[0116] The aqueous medium contained in the aqueous dispersion may be water alone or may be a mixed solvent of water and a water-compatible organic solvent. In the mixed solvent, the concentration of the water-compatible organic solvent is not particularly limited as long as it is equal to or lower than the solubility in water of the organic solvent used.
[0117] The organic solvent is not particularly limited, but examples thereof include alcohols such as methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, isobutanol, pentanol, hexanol, and heptanol; ketones such as acetone and methyl ethyl ketone; ethers such as tetrahydrofuran and dioxane; nitriles such as acetonitrile and propionitrile; amides such as dimethylformamide and acetamide; dimethyl sulfoxide; pyridine; piperidine; and the like. Among them, methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, isobutanol, acetone, methyl ethyl ketone, tetrahydrofuran, dioxane, acetonitrile, propionitrile, and the like are preferred because they are easily removed. Moreover, methanol, ethanol, 1-propanol, 2-propanol, butanol, acetone, and the like are more preferred because they are easily available. Furthermore, methanol, ethanol, and acetone are particularly preferred.
[0118] The volume average particle diameter of the PHA particles used in the preparation process is preferably within the same range as the volume average particle diameter of the above-mentioned crosslinked resin particles.When the PHA particles produced by PHA-producing microorganisms are used as raw material, the volume average particle diameter of the PHA particles can usually be within the above-mentioned range.Therefore, when the PHA particles produced by PHA-producing microorganisms are used as raw material, the aqueous dispersion of PHA particles with desired volume average particle diameter can be obtained without carrying out a special process for adjusting particle diameter.
[0119] The concentration of the PHA particles in the aqueous dispersion is not particularly limited and can be set appropriately, but may be, for example, about 1 to 70% by weight, and preferably about 5 to 50% by weight.
[0120] The aqueous dispersion of PHA particles prepared in the preparation step preferably contains a dispersant in order to increase the dispersibility of the PHA particles and to uniformly proceed with the crosslinking reaction. In other words, in the preparation step, a dispersant may be further added to the aqueous dispersion of PHA particles. Examples of the dispersant include anionic surfactants such as dioctyl sodium sulfosuccinate, sodium dodecyl sulfate, sodium lauryl sulfate, and sodium oleate; cationic surfactants such as lauryl trimethyl ammonium chloride; nonionic surfactants such as glycerin fatty acid esters, sorbitan fatty acid esters, sucrose fatty acid esters, polyoxyethylene alkyl ethers, polyoxyethylene alkyl phenyl ethers, and polyoxyethylene polyoxypropylene glycol; and water-soluble polymers such as polyvinyl alcohol, ethylene-modified polyvinyl alcohol, polyvinyl pyrrolidone, methyl cellulose, ethyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, polyacrylic acid, sodium polyacrylate, potassium polyacrylate, polymethacrylic acid, and sodium polymethacrylate. Only one of these dispersants may be used, or two or more of them may be used in combination.
[0121] When a dispersant is used, the content (addition amount) of the dispersant in the aqueous dispersion is not particularly limited. The content of the dispersant in the aqueous dispersion may be, for example, 0.1 to 10 parts by weight, preferably 0.5 to 5 parts by weight, and particularly preferably 0.5 to 3 parts by weight, based on 100 parts by weight of the resin particles.
[0122] <Impregnation process> This manufacturing method includes an impregnation step in which a peroxide is added to the aqueous dispersion of PHA particles prepared in the preparation step to impregnate the PHA particles with the peroxide. The peroxide used in the impregnation step can be any of those described above. In the impregnation step, peroxide can be added in various forms, such as solid or liquid. In addition, in the impregnation step, a liquid form of peroxide diluted with a diluent or the like can be added. In the impregnation step, the peroxide can be added all at once, or can be added continuously or in portions.
[0123] When the peroxide and the polyfunctional compound are used in combination, it is preferable to add the polyfunctional compound to the aqueous dispersion of the PHA particles in the impregnation step. The polyfunctional compound can be one of those mentioned above. The polyfunctional compound can be added in various forms such as solid and liquid. A liquid diluted with a diluent or the like may also be added. The polyfunctional compound may be added all at once, or may be added continuously or in portions.
[0124] In the impregnation step, the method of impregnating the PHA particles with the peroxide and any polyfunctional compound includes a method of setting the temperature of the aqueous dispersion of the PHA particles after or while adding these compounds to the aqueous dispersion to, for example, 0°C or higher but lower than a temperature suitable for decomposing the peroxide used in the next crosslinking step, and maintaining the temperature for, for example, about 1 minute to 5 hours while stirring the aqueous dispersion. The temperature of the aqueous dispersion during impregnation may be, specifically, about 10°C to 60°C.
[0125] The amount of peroxide used can be appropriately set in consideration of the gel fraction of the resulting crosslinked resin particles. For example, the amount of peroxide used is preferably 0.01 to 10 parts by weight, more preferably 0.1 to 8 parts by weight, further preferably 0.3 to 5 parts by weight, and particularly preferably 0.5 to 3 parts by weight, relative to 100 parts by weight of PHA particles.
[0126] According to the manufacturing method of crosslinking PHA particles in an aqueous dispersion using a peroxide, it is easy to obtain crosslinked resin particles by proceeding with crosslinking while maintaining the particle size (volume) before crosslinking. On the other hand, it may be difficult to achieve this in the method of crosslinking resin by melt kneading in the presence of a peroxide.
[0127] In addition, the manufacturing method in which PHA particles are crosslinked in an aqueous dispersion using a peroxide has the advantage that it is easy to control the temperature increase caused by the heat generated during the crosslinking reaction, and crosslinked resin particles having a safe and stable crosslinked structure (quality) can be efficiently obtained.
[0128] The amount of the polyfunctional compound used may be appropriately set in consideration of the gel fraction of the resulting crosslinked resin particles. The amount of the polyfunctional compound used is, for example, preferably 0.01 to 20 parts by weight, more preferably 0.05 to 15 parts by weight, even more preferably 0.1 to 10 parts by weight, even more preferably 0.2 to 5 parts by weight, and particularly preferably 0.3 to 3 parts by weight, relative to 100 parts by weight of the PHA particles.
[0129] In the preparation step or the impregnation step, other additives such as a dispersant, an antioxidant, a hydrolysis inhibitor, an antiblocking agent, a crystal nucleating agent, an ultraviolet absorber, etc. may be added to the aqueous dispersion. In other words, the aqueous dispersion prepared in the preparation step (or the impregnation step) may contain the various additives described above.
[0130] <Crosslinking process> This manufacturing method includes a crosslinking step in which an aqueous dispersion of resin particles impregnated with peroxide is heated to a heating temperature to crosslink the molecular chains of the resin (e.g., molecular chains of PHA). In the crosslinking step, the aqueous dispersion of PHA particles impregnated with peroxide is heated to a temperature (heating temperature) suitable for decomposing the peroxide to crosslink the molecular chains of PHA in the PHA particles.
[0131] The heating temperature in the crosslinking step is preferably within a range of about 25°C above and below the one-hour half-life temperature of the peroxide (one-hour half-life temperature -25°C to one-hour half-life temperature +25°C). Specifically, the heating temperature is preferably 30°C to 140°C, more preferably 50°C to 135°C, and even more preferably 60°C to 130°C. By setting the heating temperature within the above range, it is possible to crosslink the PHA at a temperature lower than the melting temperature of the PHA, and therefore deterioration of the PHA due to heating during the crosslinking treatment can be avoided. The melting temperature of the PHA is, for example, 50°C to 210°C.
[0132] <Maintenance process> The present production method preferably includes a maintenance step of maintaining the heating temperature after all the peroxide has been added to the aqueous dispersion. By carrying out the maintenance step, the crosslinking reaction using the peroxide can be sufficiently promoted. The time for maintaining the heating temperature is not particularly limited, but is preferably 1 minute to 15 hours, and more preferably 1 hour to 10 hours.
[0133] After the crosslinking reaction is completed, the crosslinked resin particles are separated from the aqueous dispersion, and water is removed from the separated crosslinked resin particles to obtain dried crosslinked resin particles. The method for separating the crosslinked resin particles from the aqueous dispersion is not particularly limited, and for example, filtration, centrifugation, heat drying, freeze drying, spray drying, etc. can be used. For example, spray drying can be used to obtain dried crosslinked resin particles directly from the aqueous dispersion. In addition, by extruding the crosslinked resin particles alone after separation from the aqueous dispersion, the crosslinked resin particles can be obtained in the form of pellets while completely removing the remaining moisture. In addition, an aggregation process using a coagulant and / or adjusting the pH may be performed.
[0134] The aqueous dispersion itself after the crosslinking reaction, the aqueous dispersion obtained by concentrating the aqueous dispersion after the crosslinking reaction to increase the concentration of the crosslinked resin particles, or the aqueous dispersion obtained by diluting the aqueous dispersion after the crosslinking reaction by adding an aqueous medium also constitute one aspect of the present invention. In addition, (i) an aqueous dispersion with an adjusted pH, and / or (ii) an aqueous dispersion to which other additives such as a dispersant, an antioxidant, a hydrolysis inhibitor, an antiblocking agent, a crystal nucleating agent, or an ultraviolet absorber have been added also constitute one aspect of the present invention.
[0135] The crosslinked resin particles obtained by this manufacturing method are different from the expanded resin particles disclosed in WO 2007 / 049694 and WO 2019 / 146555, and are preferably not expanded. Therefore, it is preferable that this manufacturing method does not include a step of expanding the crosslinked resin particles.
[0136] [3. Thermoplastic resin composition] In one embodiment of the present invention, a thermoplastic resin composition is provided, comprising a thermoplastic resin and the present crosslinked resin particles. In this specification, the "thermoplastic resin composition according to one embodiment of the present invention" may be referred to as the "present resin composition".
[0137] Since the resin composition has the above-mentioned structure, it is a thermoplastic resin composition that can fully enjoy the effect of improving mechanical strength such as impact strength by the crosslinked resin particles. As a result, a molded article obtained by molding the resin composition has the advantage of being excellent in tensile impact strength.
[0138] Specific embodiments of the present resin composition will be described in detail below. Note that, regarding the present resin composition, specific embodiments of the present crosslinked resin particles are the same as those described in the above section [2. Crosslinked resin particles], so the description is incorporated herein by reference and will not be described in this section.
[0139] (thermoplastic resin) The resin composition includes a thermoplastic resin. The thermoplastic resin in the resin composition can also be called a matrix resin. The thermoplastic resin is not particularly limited as long as it is a resin that can be molded into a desired shape by melting it by heating and then cooling and solidifying it. Specific examples of the thermoplastic resin include polyolefin resins such as polyethylene and polypropylene, acrylic resins such as polyvinyl chloride, polystyrene, polyvinyl acetate, polyurethane, polytetrafluoroethylene, and polymethyl methacrylic acid, AS resins, polyamides, polyacetals, polycarbonates, modified polyphenylene ethers, polyester resins, and cyclic polyolefins. These thermoplastic resins may be used alone or in combination of two or more.
[0140] As the thermoplastic resin, polyester-based resins are particularly preferred, such as aliphatic polyesters (e.g., PLA, PCL, and aliphatic polyesters having a structure in which an aliphatic diol and an aliphatic dicarboxylic acid are polycondensed, etc.) and aliphatic aromatic polyesters.
[0141] Specific embodiments of the aliphatic polyester and the aliphatic aromatic polyester are the same as those explained in the above section [2. Crosslinked resin particles], so the explanation therefor is incorporated by reference and will not be repeated here.
[0142] The crosslinked resin particles contained in the resin composition contain PHA, which is a resin having biodegradability, and are excellent in biodegradability. From the viewpoint of providing a resin composition having better biodegradability, the resin composition also preferably contains a resin having biodegradability as a thermoplastic resin, i.e., a biodegradable resin. In other words, the thermoplastic resin preferably contains a biodegradable resin. This configuration has the advantage that the biodegradability of the entire resin composition and the entire molded body obtained by molding the resin composition can be improved.
[0143] Furthermore, when the crosslinked resin particles contain a PHA (e.g., P3HB3HH) produced from a plant-derived raw material, from the viewpoint of resource circulation (carbon neutrality), it is preferable that the thermoplastic resin also contains a resin produced from a plant-derived raw material, and it is more preferable that the thermoplastic resin is composed only of a resin produced from a plant-derived raw material.
[0144] A case where the thermoplastic resin contains a biodegradable resin will be described. The thermoplastic resin preferably contains 10% by weight to 100% by weight of the biodegradable resin in 100% by weight of the thermoplastic resin. The thermoplastic resin more preferably contains 30% by weight or more of the biodegradable resin in 100% by weight of the thermoplastic resin, more preferably contains 50% by weight or more, even more preferably contains 70% by weight or more, and particularly preferably contains 90% by weight or more. The thermoplastic resin may be composed of only the biodegradable resin.
[0145] From the viewpoint of providing a resin composition and a molded article thereof having excellent impact resistance improving effect due to crosslinked resin particles, the present resin composition preferably contains an aliphatic polyester as a biodegradable resin as a thermoplastic resin component, and more preferably contains a PHA and / or polylactic acid. The PHA used as the thermoplastic resin preferably does not have a crosslinked structure.
[0146] The case where the thermoplastic resin contains PHA and / or polylactic acid as a biodegradable resin will be described below. The thermoplastic resin preferably contains 10% by weight to 100% by weight of PHA and polylactic acid in total, more preferably 30% by weight or more, even more preferably 50% by weight or more, even more preferably 70% by weight or more, and particularly preferably 90% by weight or more, based on 100% by weight of the thermoplastic resin.
[0147] The PHA that can be used as the thermoplastic resin is not particularly limited, and examples thereof include polyglycolic acid, P3HA, poly(4-hydroxyalkanoate) resins, etc. As the PHA, only one type may be used, or two or more types may be used in combination. As the PHA used as the thermoplastic resin, P3HA is particularly preferred.
[0148] A case where the crosslinked resin particles contain P3HA and the thermoplastic resin contains P3HA will be described. The P3HA that can be used as the thermoplastic resin is the same as the P3HA that can be contained in the crosslinked resin particles, and the various P3HAs described above can be used. The P3HA contained in the thermoplastic resin may be a resin with the same composition as the P3HA contained in the crosslinked resin particles, or may be a resin with a different composition and / or physical properties. The P3HA contained in the thermoplastic resin is preferably a resin with a different composition and / or physical properties from the P3HA contained in the crosslinked resin particles, and more preferably a resin that is harder than the P3HA contained in the crosslinked resin particles.
[0149] The case where the P3HA used as the thermoplastic resin contains 3-hydroxybutanoic acid (3HB) repeating units will be described. In this case, from the viewpoint of the balance between flexibility and strength, the composition ratio of the 3HB repeating units in the total monomer repeating units of P3HA (100 mol%) is preferably 80 mol% to 99 mol%, and more preferably 82 mol% to 97 mol%. When the composition ratio of the 3HB repeating units in P3HA is 80 mol% or more, the rigidity of P3HA can be improved. On the other hand, when the composition ratio of the 3HB repeating units in P3HA is 99 mol% or less, the flexibility of P3HA tends to be improved. As P3HA, two or more types having different composition ratios of the 3HB repeating units may be used in combination.
[0150] The weight average molecular weight of the PHA used as the thermoplastic resin is not particularly limited, but is preferably 50,000 to 3,000,000, more preferably 100,000 to 2,000,000, and even more preferably 150,000 to 1,500,000. When the weight average molecular weight of the PHA is 50,000 or more, sufficient rigidity and / or strength can be obtained in the present resin composition and its molded article. On the other hand, a PHA having a weight average molecular weight of 3,000,000 or less has the advantages of easy production of the PHA and excellent handling properties.
[0151] The gel fraction of the PHA, which is the thermoplastic resin component in the present resin composition, is not particularly limited, but is preferably less than 50%, more preferably 40% or less, and even more preferably 30% or less, and may be 20% or less, 10% or less, or even 0%, because of the advantages of good moldability and enhanced modification effect of the thermoplastic resin by the crosslinked resin particles. The gel fraction of the PHA is influenced by the amount of crosslinked structure that the PHA has, and specifically, the lower the gel fraction of the PHA, the smaller the amount of crosslinked structure that the PHA has. In other words, it is preferable that the PHA, which is the thermoplastic resin component in the present resin composition, is a PHA with a small amount of crosslinked structure or a PHA with no crosslinked structure.
[0152] In addition, with regard to the PHA and polylactic acid that may be contained as a thermoplastic resin in this resin composition, aspects other than those described above are the same as those explained in the section <Biodegradable resin (A)> above, so that the explanation therefor is incorporated by reference and will not be repeated here.
[0153] The content of the crosslinked resin particles in the resin composition is not particularly limited. The content of the crosslinked resin particles in the resin composition may be 0.1 parts by weight or more, 0.3 parts by weight or more, 0.5 parts by weight or more, 1 part by weight or more, 5 parts by weight or more, 7 parts by weight or more, 10 parts by weight or more, 20 parts by weight or more, 25 parts by weight or more, or 30 parts by weight or more, based on 100 parts by weight of the total of the thermoplastic resin and the crosslinked resin particles. The content of the crosslinked resin particles in the resin composition is preferably 60 parts by weight or less, more preferably 55 parts by weight or less, even more preferably 53 parts by weight or less, and particularly preferably 50 parts by weight or less, based on 100 parts by weight of the total of the thermoplastic resin and the crosslinked resin particles. The content of the crosslinked resin particles in the resin composition may be 45 parts by weight or less, 40 parts by weight or less, 30 parts by weight or less, 20 parts by weight or less, 15 parts by weight or less, 12 parts by weight or less, or 10 parts by weight or less, based on 100 parts by weight of the total of the thermoplastic resin and the crosslinked resin particles.
[0154] The content of the thermoplastic resin in the resin composition is not particularly limited. The content of the thermoplastic resin in the resin composition is preferably 40 parts by weight to 99.9 parts by weight, more preferably 40 parts by weight to 99.7 parts by weight, more preferably 40 parts by weight to 99.5 parts by weight, more preferably 40 parts by weight to 99 parts by weight, and even more preferably 40 parts by weight to 95 parts by weight, in the total of 100 parts by weight of the thermoplastic resin and the crosslinked resin particles. According to this configuration, the thermoplastic resin composition can provide a molded product having excellent impact resistance. The content of the thermoplastic resin in the resin composition may be 45 parts by weight to 93 parts by weight, 47 parts by weight to 90 parts by weight, 50 parts by weight to 80 parts by weight, 50 parts by weight to 75 parts by weight, or 50 parts by weight to 70 parts by weight, in the total of 100 parts by weight of the thermoplastic resin and the crosslinked resin particles. The content of the thermoplastic resin in the present resin composition may be 55 parts by weight or more, 60 parts by weight or more, 70 parts by weight or more, 80 parts by weight or more, 85 parts by weight or more, 88 parts by weight or more, or 90 parts by weight or more, based on 100 parts by weight of the total of the thermoplastic resin and the crosslinked resin particles.
[0155] <Nucleating agent> The present resin composition may further contain a crystal nucleating agent. When the present resin composition contains a crystal nucleating agent, in the case where the thermoplastic resin is a crystalline resin, crystallization during molding is promoted, and molding processability, productivity, etc. can be improved. Furthermore, the heat resistance and / or mechanical properties of the present resin composition and its molded product can be improved.
[0156] The crystal nucleating agent is not particularly limited, and conventionally known ones can be used. The crystal nucleating agent can be, for example, inorganic substances such as talc, kaolinite, montmorillonite, mica, synthetic mica, clay, zeolite, silica, carbon black, graphite, boron nitride, zinc oxide, titanium oxide, tin oxide, calcium carbonate, magnesium carbonate, aluminum oxide, neodymium oxide, barium sulfate, sodium chloride, and metal phosphate; sugar alcohol compounds derived from natural products such as erythritol, pentaerythritol, galactitol, mannitol, and arabitol; polysaccharides such as chitin and chitosan; polyols such as aliphatic alcohols (polyols), polyvinyl alcohol, and polyethylene oxide; sodium benzoate, potassium benzoate, lithium benzoate, calcium benzoate, magnesium benzoate, barium benzoate, lithium terephthalate, sodium terephthalate, and terephthalic acid salts. metal salts of organic carboxylic acids such as potassium phosphate, calcium oxalate, sodium laurate, potassium laurate, sodium myristate, potassium myristate, calcium myristate, sodium octacosanoate, calcium octacosanoate, sodium stearate, potassium stearate, lithium stearate, calcium stearate, magnesium stearate, barium stearate, sodium montanate, calcium montanate, sodium toluate, sodium salicylate, potassium salicylate, zinc salicylate, aluminum dibenzoate, potassium dibenzoate, lithium dibenzoate, sodium β-naphthalate, and sodium cyclohexanecarboxylate; organic sulfonates such as sodium p-toluenesulfonate and sodium sulfoisophthalate;Carboxylic acid amides such as ethylene stearic acid amide, ethylene bislauric acid amide, palmitic acid amide, hydroxystearic acid amide, erucic acid amide, and trimesic acid tris(t-butylamide), lauric acid esters, palmitic acid esters, oleic acid esters, stearic acid esters, erucic acid esters, N-oleyl palmitic acid ester, N-oleyl oleic acid ester, N-oleyl stearate ester, N-stearyl oleic acid ester, N-stearyl stearate ester, N-stearyl erucic acid ester, methylene bisstearate ester, ethylene bislauric acid ester, ethylene biscapric acid ester, ethylene bisoleic acid ester, ethylene bisstearic acid ester, ethylene biserucic acid ester, ethylene Examples of the nucleating agent include carboxylic acid esters such as butylene bisisostearate, butylene bisstearate, and p-xylylene bisstearate; dicarboxylic acid derivatives such as dimethyl adipate, dibutyl adipate, diisodecyl adipate, and dibutyl sebacate; cyclic compounds having a functional group C=O and one or more functional groups selected from the group consisting of NH, S, and O in the molecule, such as indigo, quinacridone, and quinacridone magenta; sorbitol derivatives such as bisbenzylidene sorbitol and bis(p-methylbenzylidene) sorbitol; compounds containing a nitrogen-containing heteroaromatic nucleus such as pyridine, triazine, and imidazole; phosphoric acid ester compounds, bisamides of higher fatty acids, and metal salts of higher fatty acids; branched polylactic acid; and low molecular weight poly(3-hydroxybutyrate). These crystal nucleating agents may be used alone or in combination of two or more.
[0157] The content of the crystal nucleating agent in the resin composition (when multiple crystal nucleating agents are contained, the total amount) is not particularly limited as long as it can promote the crystallization of the thermoplastic resin. The content of the crystal nucleating agent is preferably 0.05 parts by weight to 12.00 parts by weight, more preferably 0.10 parts by weight to 10.00 parts by weight, and even more preferably 0.50 parts by weight to 8.00 parts by weight, relative to 100 parts by weight of the thermoplastic resin. When the content of the crystal nucleating agent is within the above range, it is possible to obtain the effect of the crystal nucleating agent while suppressing the decrease in viscosity during molding and the physical properties of the molded product.
[0158] <Lubricant> The present resin composition may further contain a lubricant. When the present resin composition contains a lubricant, the surface smoothness of the obtained molded article can be improved. The lubricant is not particularly limited, but examples thereof include fatty acid metal salts such as magnesium stearate and calcium stearate; fatty acid amides such as behenic acid amide, stearic acid amide, erucic acid amide, oleic acid amide, methylene bisstearic acid amide, and ethylene bisstearic acid amide; polyethylene wax, oxidized polyester wax, glycerin monofatty acid esters such as glycerin monostearate, glycerin monobehenate, and glycerin monolaurate; organic acid monoglycerides such as succinic acid saturated fatty acid monoglycerides; sorbitan fatty acid esters such as sorbitan behenate, sorbitan stearate, and sorbitan laurate; polyglycerin fatty acid esters such as diglycerin stearate, diglycerin laurate, tetraglycerin stearate, tetraglycerin laurate, decaglycerin stearate, and decaglycerin laurate; and higher alcohol fatty acid esters such as stearyl stearate. The lubricant may be used alone or in combination of two or more.
[0159] The amount of lubricant used in the resin composition (when multiple lubricants are contained, the total amount) is not particularly limited as long as it can impart lubricity to the molded body. The content of the lubricant is preferably 0.01 to 20.00 parts by weight, more preferably 0.05 to 10.00 parts by weight, even more preferably 0.10 to 10.00 parts by weight, even more preferably 0.20 to 5.00 parts by weight, and particularly preferably 0.30 to 4.00 parts by weight, relative to 100 parts by weight of the thermoplastic resin. When the content of the lubricant is within the above range, it is possible to obtain the effect as a lubricant while avoiding bleeding out of the lubricant onto the surface of the molded body.
[0160] <Other ingredients> In addition to the thermoplastic resin and crosslinked resin particles, and the optionally used crystal nucleating agent and lubricant, the present resin composition may further contain other components such as plasticizers, organic fillers, inorganic fillers, antioxidants, hydrolysis inhibitors, ultraviolet absorbers, colorants such as dyes and pigments, and antistatic agents, within the scope of not impairing the functions of the resulting molded article.
[0161] The plasticizer is not particularly limited. Examples of the plasticizer include polyester-based plasticizers such as polypropylene glycol sebacate ester, aliphatic dibasic acid ester-based plasticizers such as di-1-butyl adipate, di-n-butyl sebacate, and di-2-ethylhexyl azelate, glycerin-based plasticizers such as glycerin diacetomonolaurate, glycerin diacetomonocaprylate, and glycerin diacetomonodecanoate, polycarboxylic acid ester-based plasticizers such as tri-2-ethylhexyl acetyl citrate and tributyl acetyl citrate, and polyamide-based plasticizers such as polyethylene glycol, polypropylene glycol, poly(ethylene oxide-propylene oxide) block and / or random copolymers, and polytetramethylene glycol. Examples of the plasticizer include alkylene glycol-based plasticizers, phosphoric acid ester-based plasticizers such as diphenyl-2-ethylhexyl phosphate and diphenyloctyl phosphate, epoxy-based plasticizers such as epoxidized soybean oil and epoxidized linseed oil fatty acid butyl ester, and castor oil-based plasticizers such as castor oil fatty acid esters, methyl ricinoleate, ethyl ricinoleate, isopropyl ricinoleate, butyl ricinoleate, ethylene glycol monoricylate, propylene glycol monoricylate, trimethylolpropane monoricylate, sorbitan monoricylate, castor oil fatty acid polyethylene glycol ester, castor oil ethylene oxide adduct, castor oil-based polyol, castor oil-based toluol, and castor oil-based diol. These plasticizers may be used alone or in combination of two or more.
[0162] The organic filler is not particularly limited. Examples of the organic filler include fillers made of naturally derived materials such as wood-based materials (e.g., wood chips, wood flour, sawdust, etc.), rice husks, rice flour, starch, corn starch, rice straw, wheat straw, and natural rubber; organic fibers such as natural vegetable fibers, natural animal fibers, and synthetic fibers; and fillers made of synthetic resin materials such as polyester, polyacrylic, polyamide, nylon, polyethylene, polyolefin, polyvinyl alcohol, polyvinyl chloride, polyurethane, polyacetal, aramid, PBO (poly-p-phenylene benzobisoxazole), polyphenylene sulfide, acetyl cellulose, polybenzazole, polyarylate, polyvinyl acetate, and synthetic rubber.
[0163] Examples of the natural plant fibers include kenaf fiber, abaca fiber, bamboo fiber, jute fiber, hemp fiber, linen fiber, henequen (sisal), ramie fiber, hemp, cotton, banana fiber, coconut fiber, palm, paper mulberry, mitsumata, bagasse, etc. In addition, examples of the natural plant fibers include pulp, cellulose fiber, rayon, and other regenerated fibers processed from plant fibers. Examples of the natural animal fibers include wool, silk, cashmere, mohair, etc.
[0164] The inorganic filler is not particularly limited, and examples thereof include silica-based inorganic fillers (e.g., quartz, fumed silica, silicic anhydride, fused silica, crystalline silica, amorphous silica, fillers obtained by condensing alkoxysilanes, ultrafine amorphous silica, etc.), alumina, zircon, iron oxide, zinc oxide, titanium oxide, silicon nitride, boron nitride, aluminum nitride, silicon carbide, glass, silicone rubber, silicone resin, titanium oxide, carbon fiber, mica, graphite, carbon black, ferrite, graphite, diatomaceous earth, white clay, clay, talc, calcium carbonate, manganese carbonate, magnesium carbonate, barium sulfate, silver powder, etc. These inorganic fillers may be surface-treated to increase dispersibility in the resin composition. In addition, these inorganic fillers may be used alone or in combination of two or more.
[0165] The antioxidant is not particularly limited. Examples of the antioxidant include phenol-based antioxidants, phosphorus-based antioxidants, and sulfur-based antioxidants. These antioxidants may be used alone or in combination of two or more.
[0166] The hydrolysis inhibitor is not particularly limited. Examples of the hydrolysis inhibitor include carbodiimide compounds, epoxy compounds, isocyanate compounds, and oxazoline compounds. These hydrolysis inhibitors may be used alone or in combination of two or more.
[0167] The ultraviolet absorbing agent is not particularly limited. Examples of the ultraviolet absorbing agent include benzophenone compounds, benzotriazole compounds, triazine compounds, salicylic acid compounds, cyanoacrylate compounds, and nickel complex compounds. These ultraviolet absorbing agents may be used alone or in combination of two or more.
[0168] The coloring agent such as the pigment or dye is not particularly limited. Examples of the coloring agent include inorganic coloring agents such as titanium oxide, calcium carbonate, chromium oxide, cuprous oxide, calcium silicate, iron oxide, carbon black, graphite, titanium yellow, and cobalt blue; soluble azo pigments such as lake red, lithol red, and brilliant carmine; insoluble azo pigments such as dinitrile orange and fast yellow; phthalocyanine pigments such as monochlorophthalocyanine blue, polychlorophthalocyanine blue, and polybromophthalocyanine green; condensed polycyclic pigments such as indigo blue, perylene red, isoindolinone yellow, and quinacridone red; and dyes such as oracet yellow. These coloring agents may be used alone or in combination of two or more.
[0169] The antistatic agent is not particularly limited. Examples of the antistatic agent include low molecular weight antistatic agents such as fatty acid ester compounds, aliphatic ethanolamine compounds, and aliphatic ethanolamide compounds, and polymeric antistatic agents. These antistatic agents may be used alone or in combination of two or more.
[0170] The thermoplastic resin composition may further contain, as additives, catalyst deactivators (hindered phenol compounds, thioether compounds, vitamin compounds, triazole compounds, polyamine compounds, hydrazine derivative compounds, phosphorus compounds, etc.), release agents (montanic acid and its salts, its esters, its half esters, stearyl alcohol, stearamide, polyethylene wax, etc.), color inhibitors (phosphites, hypophosphites, etc.), silane coupling agents (epoxy silane coupling agents, amino silane coupling agents, (meth)acrylic silane coupling agents, isocyanate silane coupling agents, etc.), flame retardants (red phosphorus, phosphate esters, brominated polystyrene, brominated polyphenylene ether, bromine The curable resin may also contain a curable polymer such as dimethyl ether, ...
[0171] The content of each of the other components described above is not particularly limited as long as the effect of one embodiment of the present invention is exhibited, and can be appropriately set by a person skilled in the art.
[0172] 4. Method for producing thermoplastic resin composition In one embodiment of the present invention, there is provided a method for producing a thermoplastic resin composition, comprising a mixing step of mixing the present crosslinked resin particles with a thermoplastic resin. In this specification, the "method for producing a thermoplastic resin composition according to one embodiment of the present invention" may be referred to as the "method for producing the present resin composition". The "method for producing the present resin composition" can be suitably used as a method for producing the above-mentioned "present resin composition".
[0173] The specific aspects of the crosslinked resin particles, thermoplastic resin and other components used in the method for producing the resin composition are the same as those described in the above section [3. Thermoplastic resin composition]. Therefore, the description is incorporated herein by reference and will not be repeated in this section.
[0174] <Mixing process> The method for producing the present resin composition includes a mixing step of mixing the present crosslinked resin particles with a thermoplastic resin 4 .
[0175] The mixing step is not particularly limited as long as it is a method for mixing the present crosslinked resin particles and the thermoplastic resin, and can be performed by a known method. The mixing step can be performed, for example, by a method in which the thermoplastic resin, the crosslinked resin particles, the optional crystal nucleating agent and / or nucleating agent, and other components are mixed using an extruder, a kneader, a Banbury mixer, a kneading roll, or the like. When melt-kneading, it is preferable to mix while paying attention to the decrease in molecular weight due to thermal decomposition. In addition, the thermoplastic resin composition can also be produced by dissolving all the raw materials (components) in a soluble solvent and then removing the solvent.
[0176] When producing a thermoplastic resin composition by melt kneading, each component may be individually charged into an extruder, etc., or each component may be mixed in advance and the resulting mixture may be charged into an extruder, etc. For example, an aqueous dispersion of a thermoplastic resin and an aqueous dispersion of crosslinked resin particles may be mixed, and then the resulting mixture may be dried in a dryer to obtain a mixed powder, and the mixed powder may be charged into an extruder, etc.
[0177] When melt kneading is performed using an extruder, the obtained thermoplastic resin composition may be extruded from the extruder into a strand shape and then cut, thereby processing the thermoplastic resin composition into particle shapes such as a bar shape, a cylinder shape, an elliptical cylinder shape, a sphere shape, a cube shape, a rectangular prism shape, or the like.
[0178] The resin temperature during melt kneading cannot be generally defined because it depends on the melting point and melt viscosity of the resin used, etc. The resin temperature is preferably 140°C to 250°C, more preferably 150°C to 230°C, and even more preferably 160°C to 210°C, from the viewpoint of uniformly dispersing the crosslinked resin particles in the thermoplastic resin while avoiding thermal decomposition of the thermoplastic resin.
[0179] In the method for producing the present resin composition, the amounts of the thermoplastic resin and the present crosslinked resin particles used are the contents of each component in the resulting resin composition. That is, in the method for producing the present resin composition, the amounts of the thermoplastic resin and the present crosslinked resin particles used may be appropriately adjusted in consideration of the desired contents of each component in the resin composition to be produced.
[0180] 5. Molded body In one embodiment of the present invention, a molded article is provided by molding the present resin composition. In providing a molded article according to one embodiment of the present invention, the molding method of the present resin composition is not particularly limited, and a commonly used molding method can be applied. Specific examples of the molding method include inflation film molding, extrusion blow molding, injection blow molding, extrusion molding, calendar molding, vacuum molding, injection molding, and the like. The molded article formed by molding the present resin composition can also be said to be a molded article containing the present resin composition.
[0181] By carrying out the above-mentioned molding method using the present resin composition, molded products having excellent tensile impact strength, specifically, film molded products, sheet molded products, blow molded products, extrusion molded products, vacuum molded products, and injection molded products, can be produced with good productivity. In this specification, the term "film molded product" refers to a product conforming to JIS20108:2012, specifically, a thin film having a thickness of less than 0.25 mm. In this specification, the term "sheet molded product" refers to a product conforming to JIS20108:2012, specifically, a thin plate having a thickness of 0.25 mm or more.
[0182] Molded articles containing the present resin composition can be suitably used in agriculture, fisheries, forestry, horticulture, medicine, sanitary products, the food industry, clothing, non-clothing, packaging, automobiles, building materials, and other fields. It can be suitably used in industrial, apparel, non-apparel, packaging, automotive, building materials and other fields. EXAMPLES
[0183] (Protein content) The protein content of the PHA particles and crosslinked resin particles was measured using a BCA Protein Assay Kit (manufactured by Thermo Fisher Scientific) with the aqueous dispersion of the target resin particles as a sample. Specifically, 20 to 60 mg of the aqueous dispersion sample was weighed out and placed in a screw bottle, and 2 mL of the reagent from the above kit was added, and the reaction was carried out at 60°C for 30 minutes. After the reaction, the screw bottle was immediately placed in ice water to cool it, and then filtered through a 0.2 μm filter. The protein content was measured by measuring the absorbance of the obtained filtrate at a wavelength of 562 nm.
[0184] (Volume average particle size) The volume average particle diameter of the crosslinked resin particles was measured using an aqueous dispersion of the crosslinked resin particles as a sample. A MicrotracMT3300EXII manufactured by Nikkiso Co., Ltd. was used as a measuring device. Specifically, the particle diameter and volume of each crosslinked resin particle in the aqueous dispersion of the crosslinked resin particles were measured using the above device, and the volume average particle diameter was calculated from the results obtained by the measurement based on the above-mentioned formula (1), i.e., formula (2).
[0185] (Gel fraction) The crosslinked resin particles were measured by the following method. The dried crosslinked resin particles were added to chloroform to a concentration of 0.7% by weight, and dissolved at 60°C for 30 minutes to obtain a chloroform solution. After that, the solution was left to stand at room temperature for 3 hours, and then filtered through a membrane filter with a pore size of 0.45 μm. Losses were prevented by applying chloroform to the inside of the container and on the filter multiple times while thoroughly washing the solution. The gel remaining on the filter was dried, and the weight was measured together with the filter, and the gel fraction was calculated by the following formula. Formula: Gel fraction = (weight of filter including dry gel - weight of filter only) / weight of crosslinked resin particles or uncrosslinked resin particles used in measurement x 100 (%) (Tensile impact strength) A 500 μm thick molded body prepared by the method described below was used as a sample. The sample was aged for 7 days under conditions of 23°C and 50% RH, and then punched out into test pieces having the shape specified in JIS K 71603, and the tensile impact strength was measured by a method conforming to JIS K 7160 Method A.
[0186] (Raw material for cross-linked resin particles) <Uncrosslinked resin particles> PHA-1: Poly(3-hydroxybutyrate-co-3-hydroxyhexanoate): (3-hydroxybutyrate) / (3-hydroxyhexanoate)=72 / 28 (mol / mol), weight average molecular weight Mw: 500,000 to 1.5 million <Peroxide> Di(sec-butyl) peroxydicarbonate ("Luperox 225" manufactured by Arkema Yoshitomi Co., Ltd., 1-hour half-life temperature: 69°C) <Polyfunctional compounds> Triallyl isocyanurate.
[0187] [Production Example 1: Production of PHA particles (uncrosslinked resin particles)] (inactivation) The bacterial culture solution containing PHA-1 was sterilized by heating and stirring at an internal temperature of 70°C for 8 hours.
[0188] (Enzyme treatment) To the liquid obtained above, 0.4% of an alkaline protease, Alcalase (manufactured by Novozyme), was added relative to 100% by weight of the resin solid content, and then 30% sodium hydroxide was added to adjust the pH to 9.0 while maintaining the mixture at 50° C. for 2 hours. By this operation, an enzyme-treated liquid of the bacterial cells was obtained.
[0189] (Bacterial lysis) The enzyme-treated solution obtained by the above operation was held for 3 hours while adjusting the pH to 10.5 by adding 30% sodium hydroxide. Next, sodium dodecyl sulfate (SDS, manufactured by Kao Corporation) was added to a concentration of 6.7% relative to 100% by weight of the resin solids (surfactant treatment). After that, 30% sodium hydroxide was added to adjust the pH to 11.0, and the solution was held at 40°C for 1 hour. This operation yielded a bacterial lysis treatment solution.
[0190] (Crushing) The lysis solution obtained by the above procedure was subjected to shearing for a certain period of time using a homogenizer MARKII 2.5 manufactured by Primix Corporation to disrupt the cells, thereby obtaining a disrupted solution.
[0191] (Centrifugation) The disrupted liquid obtained by the above operation was centrifuged (6900 rpm, 15 minutes), and the supernatant was removed. The same amount of sodium hydroxide aqueous solution (pH 11.0) as the removed supernatant was added thereto to redisperse the PHA particles, and the mixture was centrifuged again (6900 rpm, 15 minutes), the supernatant was removed, and then the same amount of sodium hydroxide aqueous solution (pH 11.0) as the removed supernatant was added to redisperse the PHA particles, to obtain a redispersion liquid (redispersion liquid (1)).
[0192] [Production Example 2] Except for changing the amount of sodium dodecyl sulfate added in the lysis step to 2.6% based on 100% by weight of the resin solid content, a redispersion of PHA particles was obtained in the same manner as in Production Example 1. This redispersion was used as redispersion (2) in the subsequent steps.
[0193] [Production Example 3] In the centrifugation step, after removing the supernatant after the first centrifugation, an aqueous sodium hydroxide solution (pH 11.0) was added so that the concentration of the PHA particles became 23±2% by weight, and the PHA particles were redispersed, and a redispersion of PHA particles was obtained by the same operation as in Production Example 1, except that the second centrifugation and the subsequent redispersion treatment were not performed. This redispersion was used as redispersion (3) in the subsequent operation.
[0194] Example 1 (preparation process) To the redispersion liquid (1) obtained in Production Example 1, protease (Esperase, manufactured by Novozymes) was added to a concentration of 0.07% by weight relative to 100% by weight of the resin solid content, and the mixture was kept at 45°C for 2 hours. The liquid after the enzyme treatment was centrifuged (6900 rpm, 15 minutes) and the supernatant was removed. By this operation, the protein amount in the PHA particles was adjusted. Furthermore, the PHA particles were redispersed by adding an aqueous sodium hydroxide solution (pH 11.0) in the same amount as the removed supernatant, and the mixture was centrifuged again (6900 rpm, 15 minutes) and the supernatant was removed. Finally, an aqueous sodium hydroxide solution (pH 11.0) was added so that the concentration of the PHA particles was 23±2% by weight, and the PHA particles were redispersed to obtain an aqueous dispersion of PHA particles.
[0195] (Impregnation process) The aqueous dispersion of PHA particles obtained by the above procedure (100 parts by weight in terms of solids), 200 parts by weight of deionized water, 2 parts by weight of peroxide, 1 part by weight of sodium dioctyl sulfosuccinate, and 0.5 parts by weight of a polyfunctional compound were added to a glass container equipped with a stirrer, baffle, nitrogen inlet / outlet, and thermometer, and stirring was started at room temperature while simultaneously replacing the atmosphere inside the glass container with nitrogen.
[0196] The contents of the glass container were then stirred at room temperature for 1 hour to allow the peroxide and the polyfunctional compound to be impregnated into the interior of the PHA particles. This operation resulted in an aqueous dispersion containing PHA particles impregnated with the peroxide and the polyfunctional compound.
[0197] (Crosslinking process) The aqueous dispersion obtained by the above operation was heated to a heating temperature of 75° C. After reaching 75° C., the heating temperature was maintained for 3.5 hours to crosslink the PHA in the PHA particles. This operation resulted in an aqueous dispersion in which crosslinked resin particles were dispersed in water.
[0198] The pH of the resulting aqueous dispersion of crosslinked resin particles was adjusted to 3.5 to 4.0, and then the dispersion was dried in an oven to obtain solidified crosslinked resin particles.
[0199] [Examples 2 and 4] Solidified crosslinked resin particles were obtained by the same procedure as in Example 1, except that the redispersion liquid (1) derived from a different lot of bacterial culture liquid was used.
[0200] Example 3 A redispersion (1) derived from a different lot of bacterial culture liquid was used, and the same operation as in Example 1 was performed, except that the following operation was performed. In Example 3, after obtaining an aqueous dispersion of crosslinked resin particles in the crosslinking step, the aqueous dispersion was centrifuged (5000 rpm, 5 minutes) and the supernatant was removed. The same amount of sodium hydroxide aqueous solution (pH 11.0) as the removed supernatant was added thereto to redisperse the crosslinked resin particles, and the operation of centrifuging again (5000 rpm, 5 minutes) and removing the supernatant was repeated three times to wash the PHA particles and remove proteins. Finally, the same amount of sodium hydroxide aqueous solution (pH 11.0) as the removed supernatant was added to redisperse the crosslinked resin particles. In Example 3, the protein content in the PHA particles before being subjected to the crosslinking step, in other words, the uncrosslinked PHA particles, was taken as the protein content before crosslinking of the crosslinked resin particles, and the protein content of the crosslinked resin particles after the above-mentioned washing operation was taken as the protein content after washing of the crosslinked resin particles.
[0201] Example 5 Solidified crosslinked resin particles were obtained by the same procedure as in Example 1, except that the redispersion liquid (2) was used instead of the redispersion liquid (1).
[0202] Example 6 In the step of obtaining a redispersion liquid (1) derived from a different lot of bacterial culture liquid, the same operation as in Example 1 was performed, except that the following operation was performed. In Example 6, in the centrifugation step, after removing the supernatant after the second centrifugation, a sodium hydroxide aqueous solution (pH 11.0) was added so that the concentration of the PHA particles became 23±2% by weight, thereby redispersing the PHA particles and obtaining a redispersion liquid (1'). To the redispersion liquid (1') in which the concentration of the PHA particles became 23±2% by weight without performing the protease treatment and the subsequent centrifugation treatment, a peroxide and a polyfunctional compound were added and impregnated in the same manner as in Example 1, and the subsequent crosslinking step was performed in the same manner as in Example 1.
[0203] Example 7 Solidified crosslinked resin particles were obtained by the same procedure as in Example 1, except that the redispersion liquid (3) was used instead of the redispersion liquid (1), and the following procedure was further carried out. In Example 7, in the preparation step, the second centrifugation treatment, the protease treatment, and the subsequent centrifugation treatment were not carried out, and peroxide and a polyfunctional compound were added to and impregnated into the redispersion liquid (3) in the same manner as in Example 1, and the subsequent crosslinking step was carried out in the same manner as in Example 1.
[0204] The protein content of the PHA particles obtained in each Example, and the protein content, volume average particle size, and gel fraction of the crosslinked resin particles were measured. The results are shown in Table 1. In Examples 1 to 2 and 4 to 7, the protein contents of the PHA particles (before crosslinking) and the crosslinked resin particles were the same.
[0205] [Table 1]
[0206] [Examples 8 to 13] A resin composition containing the crosslinked resin particles obtained in Examples 1 to 7 was produced.
[0207] (Raw material for resin composition) <Thermoplastic resin> PHBH (Kaneka Corporation, Kaneka Biodegradable Polymer PHBH (registered trademark), poly(3-hydroxybutyrate-co-3-hydroxyhexanoate, repeating unit composition: (3-hydroxybutyrate) / (3-hydroxyhexanoate)=94.4 / 5.6 (mol / mol), weight average molecular weight Mw: 530,000) <Crosslinked resin particles> Crosslinked resin particles prepared in Examples 1 to 5 and 7 <Nucleating agent> Pentaerythritol (NeuRizer P, manufactured by Nippon Synthetic Chemical Industry Co., Ltd.) <Lubricant> Behenamide (BNT22H manufactured by Nippon Fine Chemicals).
[0208] (Method of producing thermoplastic resin composition) For each Example, the thermoplastic resin, crosslinked resin particles, crystal nucleating agent, and lubricant shown in Table 2 were mixed in the amounts shown in Table 2 to obtain a mixture. The obtained mixture was melt-kneaded in a twin-screw extruder (KZW15TWIN-45WG manufactured by Technobel Co., Ltd.) with the barrel temperature heated to 140 to 165°C and the screw rotation speed was 80 rpm to obtain a melt-kneaded product. The obtained melt-kneaded product was dried in a dryer at 80°C for 4 hours to sufficiently reduce the moisture content, thereby obtaining the thermoplastic resin compositions of Examples 8 to 13. The thermoplastic resin composition of each Example was press-molded at 165°C to a thickness of 500 μm to produce a molded product.
[0209] Comparative Example 1 Thermoplastic resin compositions and molded articles were obtained in the same manner as in Examples 8 to 13, except that no crosslinked resin particles were used.
[0210] The tensile impact strength of the molded articles of Comparative Example 1 and each Example was measured by the above-mentioned method. The results are shown in Table 2.
[0211] [Table 2]
[0212] It is clear from Table 2 that a molded article obtained by molding a thermoplastic resin composition containing the present crosslinked resin particles has excellent tensile impact strength. In other words, it is clear that by blending the present crosslinked resin particles with a thermoplastic resin composition, it is possible to exhibit an effect of improving the tensile impact strength of a molded article obtained by molding the thermoplastic resin composition. [Industrial Applicability]
[0213] According to one embodiment of the present invention, novel crosslinked resin particles having biodegradability can be provided. The crosslinked resin particles according to one embodiment of the present invention can be suitably used as a modifier for thermoplastic resins, a spacer, an antiblocking agent, a matting agent, etc.
Claims
1. A crosslinked resin particle containing a polyhydroxyalkanoate-based resin having a crosslinked structure, The gel fraction is 50% or more, and Crosslinked resin particles having a protein content of 200 to 20,000 ppm.
2. 2. The crosslinked resin particles according to claim 1, having a volume average particle size of 0.1 μm to 10 μm.
3. 2. The crosslinked resin particles according to claim 1, wherein the polyhydroxyalkanoate-based resin is a poly(3-hydroxyalkanoate)-based resin.
4. 2. The crosslinked resin particles according to claim 1, wherein the proportion of said polyhydroxyalkanoate-based resin in said crosslinked resin particles is 80% by weight or more.
5. 2. The crosslinked resin particles according to claim 1, wherein the gel fraction is 70 to 100%.
6. 2. The crosslinked resin particles of claim 1, wherein the crosslinked resin particles are crosslinked using a peroxide.
7. 7. The crosslinked resin particles according to claim 6, wherein the crosslinked resin particles are crosslinked in the presence of the peroxide and a polyfunctional compound.
8. 2. The crosslinked resin particles of claim 1, wherein the crosslinked resin particles are non-foamed.
9. The composition contains a polyhydroxyalkanoate resin having a crosslinked structure, and A method for producing crosslinked resin particles having a gel fraction of 50% or more, comprising the steps of: A preparation step of preparing an aqueous dispersion containing polyhydroxyalkanoate-based resin particles having a protein content of 200 to 20,000 ppm; an impregnation step of adding a peroxide to the aqueous dispersion of the PHA particles to impregnate the polyhydroxyalkanoate-based resin particles with the peroxide; and a crosslinking step of heating the aqueous dispersion of resin particles impregnated with the peroxide to a heating temperature to crosslink molecular chains of the polyhydroxyalkanoate resin in the polyhydroxyalkanoate resin particles.
10. A thermoplastic resin composition comprising a thermoplastic resin and the crosslinked resin particles according to any one of claims 1 to 8.
11. The thermoplastic resin composition according to claim 10, further comprising a crystal nucleating agent and / or a lubricant.
12. A molded article obtained by molding the thermoplastic resin composition according to claim 10.
13. A method for producing a thermoplastic resin composition, comprising a mixing step of mixing a thermoplastic resin and the crosslinked resin particles according to any one of claims 1 to 8.
14. The method for producing a thermoplastic resin composition according to claim 13, wherein a crystal nucleating agent and / or a lubricant is further mixed in the mixing step.
Citation Information
Patent Citations
Vinylic crosslinked resin particle, its manufacturing method and use thereof
JP2003082191A
Matt acrylic resin film having improved design flexibility after being coated
JP2009056770A
Poly(3-hydroxyalkanoate) resin composition
WO2019022008A1